MOF nanoparticles

JP2024500350A5Pending Publication Date: 2025-01-29CAMBRIDGE ENTERPRISE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023535380
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-09
Filing Date
2021-12-09
Publication Date
2025-01-29

AI Technical Summary

Technical Problem

Known surface-functionalized nano-MOFs face challenges such as difficulty in redispersion after drying, limited shelf life due to aggregation and premature drug release, and uncontrolled drug delivery, making them unsuitable for applications like drug delivery systems.

Method used

Coating MOF nanoparticles with a polymer, such as polyethylene glycol or derivatives, through phosphate-metal coordination to enhance stability and enable tunable drug release profiles, allowing for easy redispersion and improved shelf life.

Benefits of technology

The polymer-coated MOF nanoparticles exhibit improved stability, enabling easy redispersion and tunable drug release, addressing the limitations of uncoated MOFs in drug delivery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present application relates to metal-organic framework (MOF) nanoparticles, in particular to coated MOF nanoparticles, methods for producing said coated MOF nanoparticles, and uses of said coated MOF nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to metal-organic framework (MOF) nanoparticles, in particular to coated MOF nanoparticles, a method for producing said coated MOF nanoparticles, and uses of said coated MOF nanoparticles. [Background technology]

[0002] Metal-organic framework (MOF) nanoparticles (nanoMOFs) are a relatively new family of porous and crystalline hybrid materials that have shown potential for a variety of applications, including gas storage and separation, sensing, and catalysis. In light of their tunable structure and permanent porosity, organic ligands and inorganic nodes (metal ions) provide a platform for incorporating functionality on their internal and external surfaces. In biological systems, functionalization of the external surface of nanoMOFs has been explored through post-synthetic modification for imaging and therapeutic applications.

[0003] While nano-MOFs are promising, known surface-functionalized nano-MOFs have limitations. For example, the inventors found that known surface-functionalized nano-MOFs cannot be easily redispersed when dried. Therefore, they generally need to be kept in suspension before use. This makes known surface-functionalized nano-MOFs unattractive in areas such as drug delivery. This is because known nanoparticle MOFs in solution may have a limited shelf life due to aggregation and / or premature or uncontrolled release of drugs and / or degradation of activity. Furthermore, there has been a long-standing need for drug delivery systems with tunable release profiles.

[0004] The present invention solves these and other problems associated with known MOF nanoparticles. Summary of the Invention

[0005] Thus, in a first aspect, the present invention provides a composition comprising one or more metal-organic framework (MOF) nanoparticles coated with a polymer.

[0006] Each nanoparticle contains a MOF comprising a plurality of metal ions (inorganic nodes) and a plurality of organic ligands. Preferably, the plurality of metal ions (as a plurality of metal ions) consists essentially of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, and potassium (i.e., substantially all of the metal ions in the MOF nanoparticle are the same) or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, and potassium, more preferably, the plurality of metal ions consists essentially of ions selected from zirconium and iron, and most preferably, the plurality of metal ions consists essentially of ions of zirconium or may consist of ions of zirconium.

[0007] The polymer is bound to one or more metal ions of each nanoparticle by phosphate-metal coordination. Preferably, the polymer comprises a phosphate group, more preferably, the polymer has a terminal phosphate group. Preferably, each polymer has a single terminal phosphate group. Typically, the polymer comprises a polymer (base polymer) functionalized with a phosphate group. Preferably, the base polymer is hydrophilic. Preferably, the polymer (and / or base polymer) is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof. More preferably, the polymer comprises polyethylene glycol or a derivative thereof.

[0008] In an embodiment, when the polymer comprises polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is predominantly a linear polyethylene glycol or a derivative thereof, and more preferably the polymer may essentially consist of linear polyethylene glycol or a derivative thereof, or consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not or does not comprise a branched polyethylene glycol or a branched derivative thereof.

[0009] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0010] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0011] Most preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0012] Preferably, n is about 40 to about 250.

[0013] Typically, the molecular weight of mPEG may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000).

[0014] The polymer is bound to one or more metal ions of each MOF nanoparticle, preferably substantially all of the MOF nanoparticles.Preferably, the polymer is bound to metal ions present on the outer surface of each MOF nanoparticle.Preferably, the outer surface of each MOF nanoparticle is substantially coated in the polymer.The outer surface refers to the outer surface, and does not include inner surfaces, such as the inner surfaces of the pores.

[0015] The particle size of the polymer-coated one or more MOF nanoparticles may be about 25 nm to about 450 nm, more preferably about 100 nm to about 250 nm, and most preferably about 100 nm to about 200 nm. Preferably, an active ingredient may be encapsulated in and / or present on the polymer-coated one or more MOF nanoparticles. Preferably, the active ingredient may be selected from the group consisting of pharma- ceutical active ingredients, pesticides, insecticides, and dyes.

[0016] The compositions according to the first aspect of the invention are particularly advantageous because they may have improved stability and tunable release profiles, and may facilitate lyophilization and / or dispersion of the compositions in solution such that the polymer-coated MOF nanoparticles do not significantly aggregate. The advantages of the compositions according to the first aspect of the invention are demonstrated in the examples and figures described herein.

[0017] In a second aspect, the present invention provides a dry powder pharmaceutical composition comprising one or more lyophilized, polymer-coated metal-organic framework (MOF) nanoparticles, each nanoparticle containing a MOF comprising multiple metal ions (inorganic nodes) and multiple organic ligands.

[0018] As with the previous aspect, preferably the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc and hafnium, more preferably the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium and iron, and most preferably the plurality of metal ions consists essentially of or may consist of ions of zirconium.

[0019] The polymer can bind to one or more metal ions of each nanoparticle by phosphate-metal coordination. Preferably, the polymer comprises a phosphate group, more preferably, the polymer has a terminal phosphate group. Preferably, each polymer has a single terminal phosphate group. Typically, the polymer comprises a polymer (base polymer) functionalized with a phosphate group. Preferably, the base polymer is hydrophilic.

[0020] Preferably, the polymer (and / or base polymer) is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof. More preferably, the polymer comprises polyethylene glycol or a derivative thereof.

[0021] In an embodiment, when the polymer consists of polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is mainly a linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof, or may consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not or does not contain a branched polyethylene glycol or a derivative thereof.

[0022] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0023] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0024] More preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0025] Preferably, n is about 40 to about 250.

[0026] Typically, the molecular weight of mPEG may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000).

[0027] Preferably, the particle size of the freeze-dried, polymer-coated one or more MOF nanoparticles of the second embodiment may be from about 25 nm to about 450 nm, more preferably from about 100 nm to about 250 nm, and most preferably from about 100 nm to about 200 nm.

[0028] The polymer binds to one or more metal ions of each MOF nanoparticle, preferably to substantially all of the MOF nanoparticles. Preferably, the polymer binds to metal ions present on the outer surface of each MOF nanoparticle. Preferably, the outer surface of each MOF nanoparticle is substantially coated with the polymer.

[0029] Preferably, the polymer may be bound to one or more metal ions of each nanoparticle via metal coordination, more preferably by phosphate-metal coordination.

[0030] At least one active pharmaceutical ingredient is present in and / or on the lyophilized, polymer-coated one or more MOF nanoparticles. Preferably, said one active pharmaceutical ingredient is in and / or on the one or more MOF nanoparticles prior to being coated with the polymer, and is preferably disposed by diffusion from the active pharmaceutical ingredient, typically a suspension comprising the active pharmaceutical ingredient in solution and uncoated MOF nanoparticles in suspension.

[0031] The dry powder pharmaceutical compositions according to the second aspect of the invention are particularly advantageous because they have improved stability and / or are easily redispersed in aqueous media, and the redispersed lyophilized drug-containing polymer-coated MOF nanoparticles are substantially free of aggregation. Furthermore, the release of the active drug component from the polymer-coated MOF nanoparticles can be tailored by varying the amount and / or type of coating polymer. The advantages of the compositions according to the second aspect of the invention are demonstrated in the examples and figures described herein.

[0032] Preferably, the dry powder pharmaceutical composition is provided for use in a vial, preferably the vial having a volume of about 5 ml to about 25 ml. Preferably, during manufacture, the dry powder pharmaceutical composition is lyophilized in the vial. Typically, at the time of use, the dry powder pharmaceutical composition is redispersed in the liquid vehicle in the vial.

[0033] The polymer-coated MOF nanoparticles may include a pharma- ceutical active ingredient. The pharma- ceutical active ingredient may be present in an amount of at least about 0.5%, at least about 1%, at least about 2%, or at least about 4% based on the total weight of the polymer-coated MOF nanoparticles containing a drug. In an embodiment, the ingredient is present in an amount of at most about 10%, at most about 15%, at most about 20%, at most about 25%, at most about 35%, at most about 50%, or at most about 65% based on the total weight of the polymer-coated MOF nanoparticles containing a drug. In one embodiment, the ingredient is present in an amount of at most 30% by weight based on the total weight of the polymer-coated MOF nanoparticles containing a drug. A range of about 0.5% to about 60%, or about 10% to about 50% based on the total weight of the polymer-coated MOF nanoparticles containing a drug is preferred.

[0034] Alternatively, the active pharmaceutical ingredient can be present in an amount of at most about 0.5%, at most about 1%, at most about 2%, or at most about 4%, based on the total weight of the polymer-coated, drug-containing MOF nanoparticles. The active pharmaceutical ingredient can be present in an amount of at least about 0.001%, at least about 0.005%, at least about 0.01%, at least about 0.05%, or at least about 0.1%, based on the total weight of the polymer-coated, drug-containing MOF nanoparticles.

[0035] In embodiments, the MOF nanoparticles may be at least partially amorphous, preferably substantially amorphous. For the avoidance of doubt, the metal-organic framework itself may be at least partially amorphous, preferably substantially amorphous. Preferably, the MOF nanoparticles are amorphized once the pharma- ceutical active ingredient is within the MOF nanoparticles (preferably before the MOF nanoparticles are polymer-coated, and preferably also before their lyophilization). Suitable methods for amorphizing metal-organic frameworks are disclosed below and in WO2016 / 207397, incorporated herein by reference, such as ball milling.

[0036] Amorphization aims to destroy the long-range order present in crystalline metal-organic frameworks. Amorphous metal-organic frameworks have a highly disordered framework structure and lack long-range order. However, the amorphous framework retains the basic metal-ligand connectivity that is also present in crystalline metal-organic frameworks. Amorphization may be said to result in a structural collapse of the crystalline metal-organic framework. This structural collapse may slow down or enhance the release of pharma- ceutical active ingredients from MOF nanoparticles during use.

[0037] The change of the metal-organic framework from a crystalline structure to an amorphous structure can be verified by X-ray diffraction, especially powder X-ray diffraction. Usually, crystalline metal-organic frameworks have clear Bragg reflections in the PXRD pattern. In the PXRD pattern of the amorphized metal-organic framework, these Bragg reflections are lost.

[0038] Advantageously, the inventors have discovered that amorphization complements the polymer coating of MOF nanoparticles, providing additional tunability to the release profile of the active agent (to an extent typically not achievable by either technique alone).

[0039] In a third aspect, the present invention provides a pharmaceutical composition comprising the dry powder pharmaceutical composition according to the second aspect mixed in a liquid (i.e., vehicle). A vehicle is understood to be a carrier consisting of one or more excipients for an active pharmaceutical ingredient in a liquid formulation. The pharmaceutical composition of the third aspect can be provided as a solution, suspension, or colloid, preferably as an aqueous solution, aqueous suspension, or aqueous colloid. The aqueous phase can be water, bovine serum albumin, phosphate buffered saline, plasma, Dulbecco's Modified Eagle's Medium (DMEM), Eagle's Minimum Essential Medium (EMEM), Gibco-Roswell Park Memorial Institute (RPMI) 1640 medium, McCoy's 5A medium, and / or Hank's Balanced Salt Solution (HBSS), preferably the aqueous phase is water. Usually, the dry powder pharmaceutical composition is mixed with a liquid vehicle immediately before use.

[0040] Preferably, the pharmaceutical composition further comprises a pharma- ceutically acceptable excipient, preferably the excipient is selected from the group consisting of a buffer, a stabilizer, a preservative, a colorant, a flavoring agent, a co-solvent, and combinations thereof.

[0041] In some embodiments, the pharma- ceutically acceptable excipient may be provided in a liquid vehicle that is mixed with the polymer-coated MOF nanoparticles containing the pharma- ceutically active ingredient. Additionally or alternatively, the pharma-ceutically acceptable excipient may be premixed with the polymer-coated MOF nanoparticles containing the pharma-ceutically active ingredient of the dry powder composition prior to combination with the liquid vehicle.

[0042] The pharmaceutical composition according to the third aspect of the invention is particularly advantageous since the redispersed, lyophilized, polymer-coated MOF nanoparticles do not generally aggregate. Additionally or alternatively, the active pharmaceutical ingredient may remain substantially in and / or on the polymer-coated MOF nanoparticles while in the liquid vehicle prior to administration. Furthermore, the release of the active pharmaceutical ingredient from the polymer-coated MOF nanoparticles may be tailored. This may be achieved, for example, by varying the amount of polymer coating on the outer surface of each MOF nanoparticle, which may then be varied by increasing or decreasing the duration of coating. Additionally or alternatively, the type of polymer used to coat the nanoparticles may be varied. Additionally or alternatively, the metal-organic framework of the nanoparticle MOFs may be amorphized (fully or partially) as discussed herein. The advantages of the composition according to the third aspect of the invention are demonstrated in the examples and figures described herein.

[0043] In all embodiments, the time period over which the polymer coating occurs (i.e., the coating period) can be determined by the desired properties. Typically, the coating period is sufficient to substantially saturate (e.g., substantially coat) the metal sites on the exterior surface of the MOF nanoparticles, and preferably is a period that limits or does not substantially reduce the porosity of the MOF nanoparticles. Typically, the coating period is less than about 3 hours, preferably less than about 2 hours, preferably about 1 minute to about 180 minutes, preferably about 30 minutes to about 150 minutes, preferably about 5 minutes to about 60 minutes.

[0044] Preferably, the N2 adsorption uptake of the polymer-coated nanoparticle MOF is greater than about 80%, preferably greater than about 90%, of the ideal N2 uptake.

[0045] Preferably, the polymer coating comprises less than about 40% by weight of the polymer-coated nanoparticle MOF, preferably less than about 30% by weight, more preferably between about 10% by weight and about 40% by weight, preferably between about 20% by weight and about 35% by weight.

[0046] In a fourth aspect, the present invention provides a method for producing a dry powder composition comprising one or more polymer-coated metal-organic framework (MOF) nanoparticles, each nanoparticle containing a MOF that comprises a plurality of metal ions (inorganic nodes) and a plurality of organic ligands.

[0047] As with the previous aspect, preferably the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium and potassium, more preferably the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium and iron, and most preferably the plurality of metal ions consists essentially of or may consist of ions of zirconium.

[0048] The polymer is bound to one or more metal ions. Preferably, the polymer comprises a phosphate group, more preferably, the polymer has a terminal phosphate group, preferably, the polymer has a single terminal phosphate group. Typically, the polymer comprises a base polymer functionalized with a phosphate group. Preferably, the base polymer is hydrophilic.

[0049] Preferably, the polymer is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof.

[0050] In an embodiment, when the polymer consists of polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is predominantly a linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof or may consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not and / or is substantially free of branched polyethylene glycol or a derivative thereof.

[0051] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0052] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0053] Most preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0054] Preferably, n is about 40 to about 250.

[0055] Typically, the molecular weight of mPEG (such as that of structure A) may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000).

[0056] The polymer-coated one or more MOF nanoparticles may have a particle size of about 25 nm to about 450 nm, preferably about 100 nm to about 250 nm, and most preferably about 100 nm to about 200 nm.

[0057] The method of the fourth embodiment includes the steps of: mixing a plurality of metal ions (inorganic nodes) and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; mixing the suspension of the one or more uncoated MOF nanoparticles with a polymer, whereby the polymer binds to the one or more metal ions of the one or more uncoated MOF nanoparticles to provide a suspension of one or more MOF nanoparticles coated with the polymer; and drying by lyophilization (i.e., freeze-drying).

[0058] Optionally, the method of the invention may include a concentration step to make the polymer-coated MOF nanoparticle solution more concentrated (i.e., a concentrated slurry), typically by increasing the concentration of the polymer-coated MOF nanoparticle suspension, for example by removing the solvent by centrifugation, evaporation, or other suitable methods.

[0059] Preferably, the suspension of one or more polymer-coated MOF nanoparticles has a solids content of about 1% to about 25%, preferably about 2% to about 10%, based on the total weight of the suspension before lyophilization. Preferably, the suspension is an aqueous suspension.

[0060] Preferably, the active ingredient is present in (i.e. encapsulated within) and / or present on the one or more MOF nanoparticles coated with a polymer, preferably prior to the step of mixing a suspension of one or more MOF nanoparticles not coated with a polymer with a polymer and binding the polymer to one or more metal ions of the one or more MOF nanoparticles to provide a suspension of one or more MOF nanoparticles coated with the polymer.

[0061] Preferably, an active ingredient is encapsulated in and / or disposed on the polymer-coated MOF nanoparticles or nanoparticles by mixing the active ingredient with the suspension of the uncoated MOF nanoparticles or nanoparticles. Preferably, the active ingredient may be selected from the group consisting of pharma- ceutical active ingredients, pesticides, insecticides, and dyes.

[0062] The method according to the fourth aspect of the invention is particularly advantageous since the freeze-drying step of the method provides a dry powder composition that can be subsequently redispersed in an aqueous medium with reduced aggregation of the polymer-coated one or more MOF nanoparticles, something that cannot be achieved by ambient drying. Advantageously, such a dry composition may have better shelf life than the corresponding aqueous suspension. The advantages of the method according to the fourth aspect of the invention are demonstrated in the examples and figures described herein.

[0063] Preferably, the dry powder pharmaceutical composition is provided for use in a vial, preferably the vial having a volume of about 5 ml to about 25 ml. Preferably, during manufacture, the dry powder pharmaceutical composition formed by lyophilizing a liquid slurry contained in one or more of the vials containing polymer-coated, drug-containing MOF nanoparticles, preferably a plurality of vials each containing a liquid slurry containing polymer-coated, drug-containing MOF nanoparticles, are lyophilized simultaneously.

[0064] Preferably, at the time of use, the dry powder pharmaceutical composition is redispersed in the liquid vehicle within the vial.

[0065] In a fifth aspect, the present invention provides a method of producing a suspension of polymer-coated MOF nanoparticles, the method comprising the step of taking a dry powder composition produced according to the fourth aspect and resuspending the composition in a liquid.

[0066] Preferably, the liquid is aqueous, preferably selected from the group consisting of water, bovine serum albumin, phosphate buffered saline, plasma, Dulbecco's modified Eagle's medium (DMEM), Eagle's minimum essential medium (EMEM), Gibco-Roswell Park Memorial Institute (RPMI) 1640 medium, McCoy's 5A medium, and Hank's balanced salt solution (HBSS). Preferably, the aqueous liquid is water.

[0067] The method according to the fifth aspect of the invention is particularly advantageous because it allows one or more polymer-coated MOF nanoparticles to be dispersed in a liquid such that they do not aggregate. The advantages of the method according to the fifth aspect of the invention are demonstrated in the examples and figures described herein.

[0068] In a sixth aspect, the present invention provides a method for producing a composition comprising one or more polymer-coated metal-organic framework (MOF) nanoparticles containing an active ingredient, each nanoparticle comprising a MOF that comprises a plurality of metal ions (inorganic nodes) and a plurality of organic ligands.

[0069] Preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, or potassium, more preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium and iron, and most preferably, the plurality of metal ions consists essentially of or may consist of ions of zirconium.

[0070] Preferably, the at least one active ingredient may be selected from the group consisting of pharma- ceutical active ingredients, pesticides, insecticides, and dyes.

[0071] The particle size of the MOF nanoparticles containing one or more active ingredients coated with the polymer according to the sixth embodiment may be about 25 nm to about 450 nm, preferably about 100 nm to about 250 nm, and most preferably about 100 nm to about 200 nm.

[0072] The polymer is bound to one or more metal ions by metal coordination, preferably phosphate-metal coordination. Preferably, the polymer comprises a phosphate group, more preferably the polymer is terminally terminated with a phosphate group. Typically, the polymer comprises a base polymer functionalized with a phosphate group.

[0073] Preferably, the polymer (or base polymer) may be selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof.

[0074] In an embodiment, when the polymer consists of polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is predominantly a linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof or may consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not a branched polyethylene glycol and / or is substantially free of branched polyethylene glycol.

[0075] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0076] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0077] Preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0078] Preferably, n is about 40 to about 250.

[0079] Typically, the molecular weight of mPEG (such as mPEG of Structure A) may be about 2000 g / mol to about 10000 g / mol (e.g., mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (e.g., mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (e.g., mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (e.g., mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (e.g., mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (e.g., mPEG5000).

[0080] Preferably, the polymer is bound to metal ions present on the outer surface of each MOF nanoparticle. Preferably, the outer surface of each MOF nanoparticle is substantially coated within the polymer.

[0081] The method of the sixth aspect comprises the steps of: i) mixing a plurality of metal ions (inorganic nodes) and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; ii) encapsulating an active ingredient within the one or more uncoated MOF nanoparticles to provide a suspension of one or more uncoated MOF nanoparticles containing the active ingredient; iii) then mixing the suspension of one or more uncoated MOF nanoparticles containing the active ingredient with a polymer functionalized with phosphate groups to coordinate the one or more metal ions of the one or more uncoated MOF nanoparticles containing the active ingredient to provide a suspension of one or more polymer-coated MOF nanoparticles containing the active ingredient; iv) optionally drying the one or more polymer-coated MOF nanoparticles containing the active ingredient by lyophilization; and v) optionally then redispersing the lyophilized polymer-coated MOF nanoparticles containing the active ingredient in an aqueous medium.

[0082] Preferably, the aqueous redispersion medium is selected from the group consisting of water, bovine serum albumin, phosphate buffered saline, plasma, Dulbecco's modified Eagle's medium (DMEM), Eagle's minimum essential medium (EMEM), Gibco-Roswell Park Memorial Institute (RPMI) 1640 medium, McCoy's 5A medium, and Hank's balanced salt solution (HBSS). Preferably, the aqueous redispersion medium is water.

[0083] Preferably, the suspension of MOF nanoparticles coated with one or more polymers has a solids content of about 1% to about 25%, preferably about 2% to about 10%, of the total weight of the suspension before lyophilization.

[0084] Typically, the coordination step (iii) is carried out for a time sufficient to substantially saturate the metal sites on the outer surface of the MOF nanoparticles (coating time), preferably with a polymer that limits or does not substantially reduce the porosity of the MOF nanoparticles. Typically, step iii) lasts less than about 3 hours, preferably less than about 2 hours, preferably from about 1 minute to about 180 minutes, preferably from about 30 minutes to about 150 minutes, preferably from about 5 minutes to about 60 minutes.

[0085] Preferably, the N2 adsorption uptake of the polymer-coated nanoparticle MOF is greater than about 80%, preferably greater than about 90%, of the ideal N2 uptake.

[0086] Preferably, the polymer coating comprises less than about 40% by weight of the polymer-coated nanoparticle MOF, preferably less than about 30% by weight, more preferably between about 10% by weight and about 40% by weight, preferably between about 20% by weight and about 35% by weight.

[0087] The method according to the sixth aspect of the present invention is particularly advantageous because it produces a stable suspension of one or more MOF nanoparticles containing an active ingredient coated with a polymer, which is believed to have improved stability during storage. Furthermore, when the one or more MOF nanoparticles containing an active ingredient coated with a polymer are prepared by lyophilization, the composition is stable during storage and can subsequently be redispersed to provide a suspension of one or more MOF nanoparticles containing an active ingredient coated with a polymer with reduced aggregation. The advantages of the method according to the sixth aspect of the present invention are demonstrated in the examples and figures described herein.

[0088] In a seventh aspect, the present invention provides a method for producing a composition containing one or more methoxypolyethylene glycol (mPEG) coated metal-organic framework (MOF) nanoparticles, where each nanoparticle contains a MOF that includes a plurality of metal ions (inorganic nodes) and a plurality of organic ligands.

[0089] Preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, and potassium, more preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium and iron, and most preferably, the plurality of metal ions consists essentially of or may consist of ions of zirconium.

[0090] The particle size of the one or more MOF nanoparticles coated with methoxy mPEG may be from about 25 nm to about 450 nm, preferably from about 100 nm to about 250 nm, and most preferably from about 100 nm to about 200 nm. The mPEG is bound to one or more metal ions by metal coordination, preferably phosphate-metal coordination.

[0091] Preferably, the mPEG is a phosphate-terminated mPEG according to structure A. [ka]

[0092] Preferably, n is about 40 to about 250.

[0093] Typically, the molecular weight of mPEG may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000).

[0094] The method of the seventh embodiment includes the steps of: mixing a plurality of metal ions and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; mixing the suspension of one or more uncoated MOF nanoparticles with a solution of mPEG-PO3, such that the mPEG-PO3 coordinates to the one or more metal ions of the uncoated MOF nanoparticles to provide a suspension of one or more mPEG-coated MOF nanoparticles; optionally thereafter drying the one or more mPEG-coated MOF nanoparticles by lyophilization; and optionally redispersing the lyophilized mPEG-coated MOF nanoparticles in a liquid (e.g., an aqueous medium), such as by using sonication, if necessary.

[0095] Preferably, the active ingredient is encapsulated in the one or more MOF nanoparticles coated with mPEG, preferably prior to the step of providing a suspension of said one or more MOF nanoparticles coated with mPEG-PO3 by mixing said suspension of said one or more uncoated MOF nanoparticles with a solution of mPEG-PO3 and allowing mPEG-PO3 to coordinate to one or more metal ions of said uncoated MOF nanoparticles.

[0096] Preferably, the active ingredient is encapsulated in the mPEG-coated MOF nanoparticles or nanoparticles by mixing the active ingredient with a suspension of the uncoated MOF nanoparticles or nanoparticles. Typically, the active ingredient may be selected from the group consisting of pharma- ceutical active ingredients, insecticides, pesticides, and dyes.

[0097] Preferably, the suspension of one or more MOF nanoparticles coated with mPEG has a solids content of about 1% to about 25% by weight, preferably about 2% to about 10% by weight, of the total weight of the suspension before the lyophilization step. Preferably, said suspension is an aqueous suspension.

[0098] The method according to the seventh aspect of the invention is particularly advantageous as it produces a stable suspension of one or more MOF nanoparticles coated with mPEG, which is believed to have improved stability during storage. The advantages of the method according to the seventh aspect of the invention are demonstrated in the examples and figures described herein.

[0099] In an eighth aspect, the present invention provides a composition produced according to any of the methods disclosed herein, in particular the method of the fourth, fifth, sixth or seventh aspect of the present invention. The composition may be a dry powder pharmaceutical composition comprising one or more lyophilized, polymer-coated metal-organic framework (MOF) nanoparticles. Alternatively, the composition may be a liquid suspension of one or more polymer-coated MOF nanoparticles containing an active ingredient. Optionally, the composition may be lyophilized, polymer-coated MOF nanoparticles redispersed in an aqueous medium.

[0100] The composition according to the eighth aspect of the present invention is particularly advantageous because it may provide improved stability of the MOF, facilitate lyophilization, and / or facilitate redispersion in liquid media. Furthermore, the composition may have improved stability in storage prior to use. The advantages of the composition according to the eighth aspect of the present invention are demonstrated in the examples and figures described herein.

[0101] In a ninth aspect, the present invention provides a method for producing a composition containing one or more amorphous metal-organic framework (MOF) nanoparticles containing an active ingredient, coated with a polymer. Preferably, each MOF nanoparticle is amorphous. Amorphous MOF nanoparticles may be partially and / or substantially completely amorphous. Each nanoparticle constitutes a MOF that includes a plurality of metal ions (inorganic nodes) and a plurality of organic ligands.

[0102] Preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, or potassium, more preferably, the plurality of metal ions consists essentially of or may consist of ions of a metal selected from the group consisting of zirconium and iron, and most preferably, the plurality of metal ions consists essentially of or may consist of ions of zirconium.

[0103] Preferably, the at least one active ingredient may be selected from the group consisting of pharma- ceutical active ingredients, pesticides, insecticides, and dyes.

[0104] The particle size of the polymer-coated amorphous MOF nanoparticles containing one or more active ingredients according to the ninth embodiment may be from about 25 nm to about 450 nm, preferably from about 100 nm to about 250 nm, and most preferably from about 100 nm to about 200 nm.

[0105] The polymer is bound to one or more metal ions by metal coordination, preferably phosphate-metal coordination. Preferably, the polymer comprises a phosphate group, more preferably the polymer has a terminal phosphate group, preferably the polymer has a single terminal phosphate group. Typically, the polymer comprises a base polymer functionalized with a phosphate group.

[0106] Preferably, the polymer (or base polymer) may be selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof.

[0107] In an embodiment, when the polymer consists of polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is predominantly a linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof or may consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not a branched polyethylene glycol and / or is substantially free of branched polyethylene glycol.

[0108] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0109] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0110] Preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0111] Preferably, n is about 40 to about 250.

[0112] Typically, the molecular weight of mPEG (such as mPEG of Structure A) may be about 2000 g / mol to about 10000 g / mol (e.g., mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (e.g., mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (e.g., mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (e.g., mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (e.g., mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (e.g., mPEG5000).

[0113] Preferably, the polymer is bound to metal ions present on the outer surface of each MOF nanoparticle. Preferably, the outer surface of each MOF nanoparticle is substantially coated within the polymer.

[0114] The method of the ninth aspect comprises the steps of: i) mixing a plurality of metal ions (inorganic nodes) and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; ii) encapsulating an active ingredient within the one or more uncoated MOF nanoparticles to provide a suspension of one or more uncoated MOF nanoparticles containing the active ingredient; iii) amorphizing the one or more uncoated MOF nanoparticles containing the active ingredient to form one or more amorphous (or partially amorphous) uncoated MOF nanoparticles containing the active ingredient; iv) then dissolving the one or more uncoated MOF nanoparticles containing the active ingredient in a suspension of one or more uncoated MOF nanoparticles containing the active ingredient. mixing the suspension of amorphous MOF nanoparticles with a phosphate-functionalized polymer and coordinating the phosphate-functionalized polymer to one or more metal ions of the uncoated MOF nanoparticles containing the active ingredient, thereby providing a suspension of one or more polymer-coated amorphous MOF nanoparticles containing the active ingredient; v) optionally drying the polymer-coated active ingredient-containing one or more amorphous MOF nanoparticles by lyophilization; and vi) optionally thereafter redispersing the lyophilized polymer-coated active ingredient-containing amorphous MOF nanoparticles in an aqueous medium.

[0115] Preferably, the amorphization step iii) is carried out by ball milling, heat treating or irradiating the MOF nanoparticles.

[0116] Preferably, the aqueous redispersion medium is selected from the group consisting of water, bovine serum albumin, phosphate buffered saline, plasma, and Dulbecco's modified Eagle's medium (DMEM). Preferably, said aqueous redispersion medium is water.

[0117] Preferably, the suspension of one or more polymer-coated amorphous MOF nanoparticles has a solids content of about 1% to about 25% by weight, preferably about 2% to about 10% by weight, of the total weight of the suspension before lyophilization. Preferably, the suspension is an aqueous suspension.

[0118] Typically, the coordination step iv) is carried out for a time sufficient to substantially saturate the metal sites on the outer surface of the MOF nanoparticles (coating time), preferably with a polymer that limits or does not substantially reduce the porosity of the amorphous MOF nanoparticles. Typically, step iv) lasts less than about 3 hours, preferably less than about 2 hours, preferably from about 1 minute to about 180 minutes, preferably from about 30 minutes to about 150 minutes, preferably from about 5 minutes to about 60 minutes.

[0119] Preferably, the polymer coating comprises less than about 40% by weight of the polymer-coated nanoparticle MOF, preferably less than about 30% by weight, more preferably between about 10% by weight and about 40% by weight, preferably between about 20% by weight and about 35% by weight.

[0120] The method according to the ninth aspect of the invention is particularly advantageous because it produces a stable suspension of one or more amorphous MOF nanoparticles containing an active ingredient coated with a polymer, which is believed to have improved stability during storage. The advantages of the method according to the ninth aspect of the invention are demonstrated in the examples and figures described herein.

[0121] Furthermore, amorphization can be used to further control the release of the active ingredient from the MOF nanoparticles. Without being bound by theory, it is believed that the combination of polymer coating and amorphization can provide better control of the release of the active ingredient from one or more polymer-coated amorphous MOF nanoparticles containing the active ingredient, and in particular improve the control of the release of the active ingredient compared to each technique used alone.

[0122] Furthermore, when the polymer-coated, active ingredient-containing amorphous MOF nanoparticles or nanoparticles are prepared by lyophilization, the composition is stable during storage and can subsequently be redispersed to provide a suspension of polymer-coated, active ingredient-containing amorphous MOF nanoparticles or nanoparticles with reduced aggregation.

[0123] In a tenth aspect, the present invention provides the use of a polymer functionalized with phosphate groups for coating one or more MOF nanoparticles, wherein an active ingredient is present within the one or more MOF nanoparticles to be coated.

[0124] Preferably, the polymer is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof. More preferably, the polymer comprises polyethylene glycol or a derivative thereof.

[0125] In embodiments, preferably the polymer has a terminal phosphate group, and preferably the polymer has a single terminal phosphate group.

[0126] In an embodiment, when the polymer consists of polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof. Preferably, the polyethylene glycol is predominantly a linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof or may consist of linear polyethylene glycol or a derivative thereof. Preferably, the polymer is not a branched polyethylene glycol and / or is substantially free of branched polyethylene glycol.

[0127] Preferably, the polyethylene glycol or derivative thereof contains about 40 to about 250 repeating units.

[0128] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0129] Most preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0130] Preferably, n is about 40 to about 250.

[0131] Typically, the molecular weight of mPEG may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000). Typically, the polymer binds to one or more metal ions by phosphate-metal coordination.

[0132] The use according to the tenth aspect of the invention is particularly advantageous as it may result in improved stability of the MOF nanoparticles, facilitate lyophilization and / or facilitate redispersion in liquid media. The advantages of the use according to the tenth aspect of the invention are demonstrated in the examples and figures described herein.

[0133] In an eleventh aspect, the present invention provides the use of a polymer to improve the redispersion of freeze-dried MOF nanoparticles, wherein the polymer is coated onto the MOF nanoparticles prior to freeze-drying.

[0134] Preferably, the polymer is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof. More preferably, the polymer comprises polyethylene glycol or a derivative thereof.

[0135] In embodiments where the polymer comprises polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is a linear polyethylene glycol or a derivative thereof, preferably the polyethylene glycol is predominantly linear polyethylene glycol or a derivative thereof, more preferably the polymer consists essentially of linear polyethylene glycol or a derivative thereof or may consist of linear polyethylene glycol or a derivative thereof. Preferably the polymer is not a branched polyethylene glycol or a derivative thereof.

[0136] Preferably, the linear polyethylene glycol is composed of about 40 to about 250 repeating units.

[0137] Preferably, the polymer comprises or consists essentially of a phosphate-terminated linear alkoxypolyethylene glycol (PEG), where the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, more preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises or consists essentially of a phosphate-terminated linear methoxypolyethylene glycol (mPEG).

[0138] Most preferably, the polymer is a phosphate-terminated mPEG according to structure A. [ka]

[0139] Preferably, n is about 40 to about 250.

[0140] Typically, the molecular weight of mPEG may be about 2000 g / mol to about 10000 g / mol (mPEG2000 to mPEG10000), preferably about 3000 g / mol to about 9000 g / mol (mPEG3000 to mPEG9000), about 4000 g / mol to about 8000 g / mol (mPEG4000 to mPEG8000), about 5000 g / mol to about 7000 g / mol (mPEG5000 to mPEG7000), or about 5000 g / mol to about 6000 g / mol (mPEG5000 to mPEG6000). Preferably, the molecular weight of mPEG is about 5000 g / mol (mPEG5000). Typically, the polymer binds to one or more metal ions by metal coordination, preferably metal phosphate coordination.

[0141] The use according to the eleventh aspect of the invention is particularly advantageous since it may improve the redispersion of the MOF nanoparticles. The advantages of the use according to the eleventh aspect of the invention are demonstrated in the examples and figures described herein.

[0142] In a twelfth aspect, the present invention provides a method of treating a disease or condition by administering to a patient a composition according to the first, second, third and eighth aspects of the invention.

[0143] In a thirteenth aspect, the present invention provides a composition according to the first, second, third and eighth aspects of the invention for use in therapy.

[0144] In a fourteenth aspect, the present invention provides the use of a composition according to the first, second, third and eighth aspects of the invention for the manufacture of a medicament. [Brief description of the drawings]

[0145] The present invention will now be described with reference to the following figures, which are not intended to be limiting of the invention. [Figure 1] FIG. 1 is a schematic diagram of the synthesis of PCN-222 and PCN-222@PEG-PO3. [Diagram 2] Simulated PXRD pattern of PCN-222 and experimental PXRD patterns of PCN-222, PCN-222@PEG-PO3, and mPEG-PO3. [Diagram 3] 31P SSNMR spectra of PCN-222@PEG-PO3 and mPEG-PO3. [Figure 4] Figure 1 shows the XPS survey spectra of PCN-222@PEG-PO3 and PCN-222. [Diagram 5] High-resolution Zr 3d spectra of PCN-222 and PCN-222@PEG-PO3. [Figure 6] Figure 1 shows the intensity-average diameter of the suspension of PCN-222 (green line), PCN-222@PEG-PO3 (blue line), and redispersion of PCN-222@PEG-PO3 (pink line) in water (n = 3). [Figure 7] FIG. 1 shows the zeta potential of aqueous suspensions of PCN-222 and PCN-222@PEG-PO3. [Figure 8] This is a TEM image of drop-cast PCN-222. [Figure 9] TEM image of drop-cast PCN-222@PEG-PO3. [Figure 10] SEM images of freeze-dried PCN-222@PEG-PO3, and the insets are optical images of freeze-dried PCN-222@PEG-PO3 (left) and its redispersion (right). Scale bar is 500 nm. [Figure 11] Proposed schematic diagram of PCN-222@PEG-PO3 formation. [Figure 12] Simulated and experimental PXRD patterns are shown. Characterization recorded at different time intervals (2 h, 4 h, 12 h, and 16 h). [Figure 13] N2 isotherm at 77 K. Characterization recorded at different time intervals (2 h, 4 h, 12 h, and 16 h). [Figure 14] The PSD obtained with the NLDFT method is shown. Characterization recorded at different time intervals (2 h, 4 h, 12 h, and 16 h). [Figure 15] Simulated and experimental PXRD patterns of PCN-222(Hf). [Figure 16] FIG. 1 shows a HAADF-STEM image of PCN-222(Hf). The scale bar is 500 nm. [Figure 17] Simulated PXRD patterns of UiO-66, MOF-808, NU-901, and PCN-128, and experimental PXRD patterns of UiO-66 and UiO-66@PEG-PO3, MOF-808 and MOF-808@PEG-PO3, NU-901 and NU-901@PEG-PO3, and PCN-128 and PCN-128@PEG-PO3. [Figure 18] SEM image of freeze-dried UiO-66@PEG-PO3. [Figure 19] SEM image of freeze-dried MOF-808@PEG-PO3. [Figure 20] SEM image of freeze-dried NU-901@PEG-PO3. [Figure 21] SEM image of freeze-dried PCN-128@PEG-PO3. [Figure 22] Intensity-average diameter (n=3) of suspensions of parent nanoMOFs (green line), MOFs@PEG-PO3 (blue line), and redispersed suspensions of MOFs@PEG-PO3 (pink line) in water. MOFs=UiO-66, MOF-808, NU-901, and PCN-128. Scale bar is 500 nm. [Diagram 23] 1H NMR spectrum of mPEG-PO3. [Figure 24] 31P NMR spectrum of mPEG-PO3. [Diagram 25]GPC trace of mPEG-PO3(5k). [Figure 26] FIG. 1 shows SEM images of PCN-222 with different sizes depending on the amount of TFA added. [Figure 27] TEM and HAADF-STEM images (inset) of PCN-222. Scale bars, 500 nm (left), 200 nm (right) (inset, 15 nm). [Figure 28] TEM and HAADF-STEM images (inset) of PCN-222@PEG-PO3. Scale bars, 500 nm (left), 200 nm (right) (inset, 15 nm). [Figure 29] SEM images of a: UiO-66, b: MOF-808, c: NU-901, and d: PCN-128. Inset in b, 300 nm. [Diagram 30] Optical images of the same mass (60 mg) of PCN-222@PEG-PO3 a: air-dried and b: freeze-dried. [Diagram 31] SEM images of air-dried PCN-222@PEG-PO3 at different magnifications. [Diagram 32] SEM images of freeze-dried PCN-222@PEG-PO3 at different magnifications. [Diagram 33] FT-IR spectra, where a is the full spectrum and b is the expanded spectrum. [Diagram 34] TGA profiles of PCN-222@PEG-PO3: a: 2 h PEGylation, b: 4 h PEGylation, c: 12 h PEGylation, and d: 16 h PEGylation. [Diagram 35] P 2p XPS spectrum of PCN-222@PEG-PO3. [Diagram 36] XPS spectra of PCN-222(Hf) and PCN-222(Hf)@PEG-PO3: a) XPS survey spectrum, and b) high-resolution P 2p spectrum of PCN-222(Hf)@PEG-PO3. [Figure 37]Figure 2 shows N2 adsorption isotherms and PSDs of PCN-222 and that PEGylated for 2 hours, where a and b show the results before subtracting the mPEG-PO3 content, and c and d show the results after subtracting the mPEG-PO3 content. [Figure 38] N2 adsorption isotherms and PSDs of the PEGylated product after 4, 12, and 16 hours (a, b before subtracting the mPEG-PO3 content, c, d after subtracting the mPEG-PO3 content). [Figure 39] N2 adsorption isotherms and PSDs of PCN-222 and the PEGylated product after 16 hours, a and b show the results before adsorption, and c and d show the results after subtracting the mPEG-PO3 content. [Diagram 40] 1 shows the N2 adsorption isotherm of PCN-222(Hf). [Diagram 41] Figure 2 N2 isotherms and PSDs of MOF@PEG-PO3: a: UiO-66@PEG-PO3, b: MOF-808@PEG-PO3@PEG-PO3, c: NU-901@PEG-PO3, and d: MOF-128@PEG-PO3. [Figure 42-1] Figure 1 shows the long-term dispersion of bare MOF (green line) and MOF@PEG-PO3 when suspended in H2O and PBS, respectively. n=3. [Figure 42-2] Figure 1 shows the long-term dispersion of bare MOF (green line) and MOF@PEG-PO3 when suspended in H2O and PBS, respectively. n=3. [Diagram 43] FIG. 1 shows the controlled release profile of doxorubicin (DOX) from PCN-222 and PCN-222@PEG-PO3. [Diagram 44] UV-visible spectra of DOX before and after MOF encapsulation and PEGylation. [Diagram 45] Figure 14 shows the cumulative release profiles of DOX from DOX@MOF and DOX@MOF@PEG-PO3 in PBS (pH = 7.4). Detailed Description of the Invention

[0146] The present invention relates to metal-organic framework (MOF) nanoparticles, in particular to coated MOF nanoparticles, a method for producing said coated MOF nanoparticles, and uses of said coated MOF nanoparticles.

[0147] Metal-organic frameworks (MOFs) are crystalline materials that consist of metal ions, such as metal cations, coordinated with multidentate organic ligands. MOF structures are characterized by an open framework that can be porous.

[0148] MOF nanoparticles consist of metal-organic frameworks and may have a three-dimensional structure. The MOF nanoparticles disclosed herein may be generally rod-shaped, spherical, or cubic. Preferably, the MOF nanoparticles disclosed herein are generally rod-shaped. The polymer-coated MOF nanoparticles of the present invention each contain a MOF that includes multiple metal ions (inorganic nodes) and multiple organic ligands. The polymer may then be bound to one or more metal ions of each nanoparticle.

[0149] The preferred MOF nanoparticles according to the present invention may be PCN-222, UiO-66, MOF-808, NU-901, and PCN-128, more preferably PCN-222. The coated MOF nanoparticles are named MOF@polymer. For example, PCN-222, whose polymer coating is mPEG attached via phosphate coordination, is designated PCN-222@mPEG-PO3.

[0150] The particle size of the MOF nanoparticles coated with one or more polymers is about 25 nm to about 450 nm. For the avoidance of doubt, unless otherwise specified, the particle size disclosed herein relates to the coated MOF nanoparticles. Preferably, the particle size of the MOF nanoparticles coated with one or more polymers is about 100 nm to about 250 nm, more preferably about 100 nm to about 200 nm.

[0151] The particle size of one or more polymer-coated MOF nanoparticles can be measured according to the dynamic light scattering (DLS) method disclosed herein. Particle size refers to the hydrodynamic diameter and can be defined as the radius of a hypothetical sphere diffusing at the same rate as the particle under investigation.

[0152] Preferably, the uncoated MOF nanoparticles are substantially monodisperse. The uncoated MOF nanoparticles may have, for example, a polydispersity index of less than about 0.250 nm, less than about 0.120 nm, preferably from about 0.100 nm to about 0.250 nm.

[0153] Typically, the MOF nanoparticles contain only a single type of metal ion. Thus, the plurality of metal ions (inorganic nodes) may consist essentially of (or consist of) ions of a metal selected from the group consisting of zirconium, iron, zinc, hafnium, magnesium, and potassium. The plurality of metal ions (inorganic nodes) may consist essentially of (or consist of) ions of a metal selected from the group consisting of zirconium and iron. Preferably, the plurality of metal ions consists essentially of (or consist of) ions of zirconium. Typically, the selected metal ions are biocompatible or pharma- ceutical acceptable.

[0154] The organic ligands contained in the MOF according to the present invention may be polydentate ligands. Polydentate organic ligands are organic ligands that can donate two or more pairs of electrons in a complexation reaction to form two or more coordinate bonds. The organic ligands may contain two or more oxygen atoms and / or nitrogen atoms suitable for donating a pair of electrons to form two or more coordinate bonds. Preferably, the oxygen atoms can be present as carboxylate groups or nitro groups. Preferably, the nitrogen atoms can be present as amine groups. Typically, the multiple organic ligands can be aromatic carboxylates, aromatic amines and / or aromatic nitros. Preferably, the organic ligands may be selected from the group consisting of tetrakis(4-carboxyphenyl)porphyrin (TCPP), 1,4-benzenedicarboxylic acid (BDC), 1,3,5-benzenedicarboxylic acid (H3BTC), 1,3,5,8-(p-benzoate)pyrene linker (H4TBAPy), and 4',4"',4'"",4'"""-(ethene-1,1,2,2-tetrayl)tetrakis(([1,1'-biphenyl]-3-carboxylic acid)) (H4ETTC). Typically, the organic ligand selected will be biocompatible or pharma- ceutically acceptable.

[0155] The polymer can be bound to one or more metal ions of each nanoparticle by phosphate-metal coordination. Advantageously, this provides a relatively strong bond without the need for complex chemistry. Polymers for the purposes of the present invention can have 40 or more repeat units and can include homopolymers and copolymers, including alternating, periodic, random, block, and graft copolymers. Preferably, the polymer is substantially linear. Branched polymers are typically not preferred. Typically, the polymer selected will be biocompatible or pharma- ceutical acceptable.

[0156] Generally, oligomers are not included. For the purpose of the present invention, oligomers are understood to be molecules that contain several repeat units, such that the properties of the molecule change significantly by removing one or several units. Oligomers can contain 30 or less repeat units, for example 10 or less repeat units. In particular, oligonucleotides and cyclodextrins can be excluded.

[0157] Preferably, the polymer is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof. Typically, the polymer contains phosphate groups, preferably terminal phosphate groups. Preferably, the polymer is substantially unbranched.

[0158] Preferably, the base polymer is hydrophilic.

[0159] The polymer may have a molecular weight (Mw) of about 2000 g / mol to about 10000 g / mol, preferably about 3000 g / mol to about 9000 g / mol, about 4000 g / mol to about 8000 g / mol, about 5000 g / mol to about 7000 g / mol, or about 5000 g / mol to about 6000 g / mol. The molecular weight can be determined using gel permeation chromatography as described herein.

[0160] More preferably, the polymer comprises polyethylene glycol or a derivative thereof, preferably a phosphate group-terminated alkoxypolyethylene glycol (alkoxy PEG), wherein the alkoxy group is preferably an alkoxy having 1 to 5 carbon atoms, preferably an alkoxy having 1 to 3 carbon atoms. Even more preferably, the polymer comprises a phosphate group-terminated methoxypolyethylene glycol (mPEG).

[0161] Most preferably, the polymer is a phosphate-terminated mPEG with structure A. Preferably, n is from about 40 to about 250. [ka]

[0162] Without being bound by theory, it is believed that the phosphate-terminated polymer displaces the active ingredient adsorbed on the surface of the MOF nanoparticle. This is particularly advantageous because the phosphate-terminated polymer can help to remove excess active ingredient from the surface of the MOF nanoparticle while retaining the active ingredient encapsulated in the MOF nanoparticle, and control the release of the active ingredient from the MOF nanoparticle. Therefore, without being bound by theory, it may be particularly advantageous to carry out the active ingredient encapsulation step before the polymer coating step.

[0163] An active ingredient is an agent that provides an intended effect under the conditions of intended use of the MOF nanoparticle, and is typically used in the environment external to the MOF nanoparticle. Active ingredients according to the present invention may be pharma- ceutical active ingredients, pesticides, insecticides, fragrances, and dyes.

[0164] A pharma- ceutical active ingredient is an ingredient that has a therapeutic or prophylactic effect on a disease or condition of the human or animal body.

[0165] Non-limiting examples of pharma- ceutical active ingredients suitable for use in the present invention include antibiotics, analgesics, alpha-blockers, antiallergy agents, antiasthmatics, (allergic rhinitis agents, chronic urticaria agents), anti-inflammatory agents, antacids, anthelmintics, antiarrhythmic agents, antiarthritic agents, antibacterial agents, anxiolytics, anticoagulants, antidepressants, antidiabetic agents, antidiarrheal agents, antidiuretics, antiepileptic agents, antifungal agents, antigout agents, antihypertensive agents, antiincontinence agents, antiinsomnia agents, antimalarial agents, antimigraine agents, antimuscarinic agents, antineoplastic and immunosuppressive agents, antiprotozoal agents, antirheumatic agents, antirhinitis agents, anticonvulsants, antithyroid agents, antiviral agents, antianxiety agents, sedatives, hypnotics and neuroleptics, beta-blockers, antiprostatic hyperplasia (BHP), cardiac stimulants, corticosteroids, cough suppressants, fibromyalgia agents, and the like. Cytotoxic agents, nasal decongestant, diuretics, enzymes, anti-Parkinson's agents, gastrointestinal agents, histamine receptor antagonists, hormone replacement therapy, lipid regulators, local anesthetics, neuromuscular agents, nitrates and anti-anginal agents, anti-pain agents, anti-nausea agents, nutritional agents, opioid analgesics, vaccines, proteins, peptides and recombinant drugs, prophylaxis of chemotherapy-induced and post-operative nausea and vomiting, proton pump inhibitors, sex hormones and contraceptives, spermicides, veterinary drugs, agents for treating diabetic gastric stasis, agents for treating infertility, agents for treating endometriosis, agents for treating menstrual disorders, agents for treating motion sickness, agents for treating movement disorders, agents for treating schizophrenia, agents for treating seizures and panic disorders, agents for treating sexual dysfunction (male and female), agents for treating irritable voiding disorders, etc., or combinations thereof. The use of cytotoxic pharmacoactive ingredients useful in the treatment of cancer is particularly preferred.

[0166] The pharmaceutical composition can be provided as a solid, a suspension, preferably a dry powder, or an aqueous suspension. A suspension herein includes a colloidal suspension. Preferably, the suspension is a colloidal suspension. This can be confirmed by observing the Tyndall effect using a red laser.

[0167] The pharmaceutical composition may further comprise one or more pharma- ceutically acceptable excipients, preferably selected from the group consisting of solvents, cosolvents, buffers, stabilizers, antioxidants, preservatives, chelating agents, emulsifiers, flavorings, lubricants, suspending agents, isotonicity agents, surfactants, solubilizers, suspension aids, dispersants, moisturizers, thickeners, colorants, wetting agents, antifoaming agents, viscosity adjusters, sweeteners, and combinations thereof.

[0168] The dry powder pharmaceutical compositions of the present invention may comprise about 50% to about 100% by weight, about 60% to about 90% by weight, or about 70% to about 80% by weight of lyophilized, polymer-coated MOF nanoparticles containing a pharma- ceutical active ingredient as a percentage of the total composition.

[0169] Preferably, the lyophilized, polymer-coated MOF nanoparticles containing a pharma- ceutical active ingredient release less than about 30% by weight of the active ingredient over the first 6 hours in aqueous solution, preferably less than about 25% by weight, more preferably less than about 20% by weight, typically in Dulbecco's PBS, pH 7.4 at 25°C.

[0170] The method of administration of the pharmaceutical composition according to the present invention includes oral, parenteral (e.g., intravenous, subcutaneous, intramuscular, intraarticular), cutaneous (e.g., topical), or inhalation administration, with intravenous administration being particularly preferred. The pharmaceutical composition may be a liquid composition.

[0171] Lyophilization (also called freeze-drying or cryodessication) is a drying process carried out at low temperatures. In general, lyophilization involves lowering the temperature and pressure below the triple point of the substance, and removing the frozen solvent (such as water ice) by sublimation. For aqueous compositions as disclosed herein, lyophilization can be carried out at temperatures of about -50°C to -80°C, preferably about -70°C, and pressures of about 1000 Pa (0.01 bar) to about 100 Pa (0.001 bar), preferably about 800 Pa (0.008 bar).

[0172] Preferably, lyophilization is performed on a concentrated aqueous slurry of polymer-coated MOF nanoparticles, typically the aqueous slurry is lyophilized in multiple vials having a volume of about 5 ml to about 25 ml.

[0173] Redispersion is a process in which a previously dried solid material (e.g., a freeze-dried composition of the present invention) is dispersed in a suspension two or more times. Preferably, the redispersed suspension is a colloidal suspension. Typically, a colloidal suspension is stable for at least one week.

[0174] If the polymer-coated nanoparticle MOF contains an encapsulated active ingredient, it is preferably washed between the condensation step and lyophilization to remove excess unencapsulated active ingredient, typically with water. EXAMPLES

[0175] The invention will now be demonstrated by reference to the following non-limiting examples.

[0176] Unless otherwise specified, room temperature is 20°C (293.15K, 68°F) and pressure is 1atm (14.696psi, 101.325kPa). Experimental Methods Where referred to in this document, the following methods and procedures were employed. Powder X-ray Diffraction (PXRD)

[0177] Powder X-ray diffraction (PXRD) data were collected on a Bruker D8 DAVINCI diffractometer at 298 K (24.85° C.) using CuKα radiation. Calculated PXRD patterns were generated using the Mercury program and single crystal reflection data. Thermogravimetric analysis (TGA)

[0178] The measurements were performed using a TA Instruments Q500 Thermogravimetric Analyzer. Measurements were collected from room temperature to 800° C. at a heating rate of 5° C. / min under nitrogen. Gas intake

[0179] N2 adsorption isotherm measurements were performed at 77 K (-196.15 °C) using a Micromeritics 3Flex analyzer. Samples were degassed under vacuum at 120 °C for 20 h using a built-in turbo pump. BET areas were estimated by applying the Brunauer-Emmett-Teller (BET) equation. Dynamic Light Scattering (DLS)

[0180] Measurements were recorded at 25°C in water suspension with a Zetasizer NanoZS, (Malvern Instrument Ltd., UK) equipped with a He-Ne laser operating at 633 nm, and analysed using the Zetasizer Software. Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES)

[0181] ICP-OES was performed using a Perkin Elmer ICP-OES Optima 2100DV. Samples were dispersed in 2 mL of nitric acid and 6 mL of hydrochloric acid and left at room temperature in a fume hood for at least 1 h until all reactions had ceased. Samples were then heated at 90°C for 10 h to ensure complete digestion. Samples were diluted 750-fold before measurement. X-ray photoelectron spectroscopy (XPS)

[0182] XPS analysis was performed using a Thermo Fisher Scientific ESCALAB 250Xi XPS system. A monochromatic Al-Kα source (1486.74 eV) and charge neutralizer were used for all samples. Survey scans were acquired with a pass energy of 100 eV, 1 scan, and a dwell time of 50 ms. High-resolution data were acquired with a pass energy of 50 eV, 50 scans, a dwell time of 50 ms, and standard magnetic lenses. Liquid nuclear magnetic resonance spectroscopy (NMR)

[0183] Liquid crystal NMR was performed using a Bruker 400 MHz Avance III HD Smart Probe Spectrometer. Solid state nuclear magnetic resonance spectroscopy (NMR)

[0184] Solid-state NMR experiments were performed using a 4.7 T magnet (corresponding to the Larmor frequency: ν( 1 H) = 200 MHz and ν0( 31 Spectroscopy was performed on a Bruker Avance III 200 MHz spectrometer equipped with a 1.3 mm double-channel magic-angle spinning (MAS) probe. The spinning frequency was 60 kHz. Spectra were acquired using rotor-synchronous Hahn echo experiments with excitation and refocusing pulse lengths optimized to 1.56 μs and 3.12 μs, respectively. A 1 s recycle delay was used in all experiments, and 4096 (mPEG-PO3 samples) or 8192 (MOF samples) transients were collected. Spectra were processed with 50 Hz exponential apodization, zero-filling, and then Fourier transformed. 31 P chemical shifts are measured using 85% H3PO4 in H2O (δ iso ( 31 P) = 0 ppm. UV-Visible Fluorescence Spectroscopy

[0185] UV-visible and fluorescence spectra were recorded using a Tecan Spark® Multimode Microplate Reader. Fourier transform infrared spectroscopy (FT-IR)

[0186] FT-IR was performed using a Bruker Tensor 27 FTIR with attenuated total reflectance (ATR). Gel Permeation Chromatography (GPC)

[0187] GPC was performed on a Shimadzu HPLC system consisting of an LC-20AD Pump, a SIL-20A autosampler, a CTO-20A column oven, and a CBM-20A control unit. Scanning Electron Microscope (SEM)

[0188] Samples for SEM testing were coated with Pt or Au for 40 seconds and imaged using an FEI Nova Nano SEM 450. Transmission electron microscope (TEM)

[0189] Samples for TEM testing were prepared by ultrasonically dispersing them in ethanol. A small amount of the suspension was then drop-cast onto a carbon-supported copper grid. TEM micrographs were collected on a Tecnai F20 at an accelerating voltage of 200 kV. High angle dark field scanning transmission electron microscope (HAADF-STEM) imaging

[0190] Samples were prepared by wet dispersion method from aqueous solutions. Scanning transmission electron microscopy (STEM) was performed on a FEI Tecnai Osiris at 200 kV with a OneView CMOS camera. Energy dispersive X-ray (EDX) chemical maps were acquired using a Super-X detector setup with a total acquisition solid angle of 0.9 sr. EDX data were analyzed using ES Vision. Size Exclusion Chromatography with Multi-Angle Light Scattering (SEC-MLAS)

[0191] SEC-MLAS was performed on a Shimadzu HPLC system consisting of an LC-20AD Pump, a SIL-20A autosampler, a CTO-20A column oven, and a CBM-20A control unit. The column set consisted of 1x PSS SUPREMA analytical 100 Å (8 × 300 mm) and 2x PSS SUPREMA analytical 3000 Å (8 × 300 mm). Dual detection was achieved with a Wyatt DAWN HELEOS-II multi-angle light scattering (MALS) detector (laser at λ = 658 nm) and a Wyatt Optilab rEX differential refractive index (DRI) detector (658 nm light source). MilliQ Water containing 0.1 mol / L sodium nitrate and 0.01 mol / L sodium azide was used as the eluent at a flow rate of 1.0 mL / min. The column and detector temperatures were kept at 30 °C. All data analysis was performed using Wyatt Astra V6.1.1 software. The molecular weights of all samples were determined using the literature value of dn / dc for poly(ethylene glycol) in water (0.134 ml / g) (see Hasse et al., Macromolecules 1995, 28(10), 3540-3552). Molecular Dynamics (MD) Simulation

[0192] The structure of PCN-222 was taken from the work of Feng et al. (Angew. Chem. Int. Ed. 2012, 51(41), 10307-10310). The structure of mPEG-PO3 (consisting of 128 monomer units) was created in Material Studio. Geometry optimization of both the polymer and the framework was performed using the Forcite module in Materials Studio. The charges on the framework and PEG were calculated using the EQeq protocol (see Wilmer et al., J. Phys. Lett. 2012, 3(17), 2506-2511). All simulations were performed using the LAMMPS (Plimpton, J. Comput. Phys. 1995, 117(1), 1-19.) molecular dynamics package, using Universal Force Field (UFF) (Rappe et al., J. Am. Chem. Soc. 1992, 114(25), 10024-10035) parameters to describe the Lennard-Jones, bond, angle, dihedral and improper torsion potentials. The simulation box consists of a 2x2x2 cell of PCN-222 (which is believed to be large enough to avoid finite size effects) and one mPEG-PO3 chain placed on the outer surface of the framework. Periodic boundary conditions are applied in all three dimensions. The model is first energy minimized (equilibration run) using the NVE ensemble until a temperature of 298 K (24.85 °C) is reached. It is then run for a period of 1.5 ns using the canonical ensemble (NVT). All MD simulations are performed using a time step of 1 fs. The temperature was maintained using the Nose-Hoover thermostat (Evans et al., J. Chem. Phys. 1985, 83(8), 4069-4074) with a damping factor of 0.1 ps. Long-range electrostatic interactions are calculated using Ewald summation to an accuracy of 1 × 10 -4The nonbonded van der Waals interactions were calculated using the Lennard-Jones potential, and the short-range electrostatic interactions were calculated using a Coulomb potential, both with a cutoff of 12.5 A. Trajectories were sampled every 0.01 ns and displayed using VMD (see Humphrey et al., J. Mol. Graph. 1996, 14(1), 33-38). Materials and Synthesis

[0193] Unless otherwise noted, all reagents were obtained from commercial sources and used without further purification. Synthesis of mPEG5K-phosphate (mPEG-PO3) [ka]

[0194] Poly(ethylene glycol) methyl ether (Mn=5000, 37.0 mmol) was dissolved in 150 mL of dry tetrahydrofuran (THF) and POCl3 (44.4 mmol, 1.2 equiv) was added dropwise with stirring. The resulting solution was heated to 60°C under a stream of N2 for 10 h to remove HCl formed during the reaction. After cooling to room temperature, distilled water (40 ml) was added, after which the mixture was reheated to 60°C for an additional 3 h and cooled to room temperature again. The THF was removed under vacuum and the material was purified by dialysis using dialysis tubing with a molecular weight cutoff of 3,500, followed by removal of residual water to give mPEG-PO3 as a white solid (154.8 g, 31.45 mmol, 85%). 1 H NMR(D2O,400MHz),δ:3.63(s,448H,-CH2OCH2-),3.31(s,3H,-OCH3) 31 P NMR δ: (DO, 162MHz) δ: 0.22. Synthesis of Zr6 cluster

[0195] Zr6 cluster was synthesized following a reported procedure (Noh et al., Chem. Mater. 2018, 30(7), 2193-2197). 15 ml of an 80% solution of Zr(OBu)4 (5 mmol) in n-butanol was added to a solution of 100 g (818.8 mmol) of benzoic acid in 300 ml of n-propanol, resulting in a clear mixed solution. The mixture was further refluxed overnight, and a white solid precipitate appeared. After filtration, 10.2 g (yield: 63%) of solid was isolated, washed five times with anhydrous n-propanol, and dried under vacuum. Size-controlled synthesis of PCN-222 nanoparticles

[0196] Tetrakis(4-carboxyphenyl)porphyrin (TCPP) (22.5 mg, 28.5 μmol), Zr6 cluster (38 mg, 14.2 μmol), 8 mL of DMF, and X μL of TFA were dissolved by ultrasonication in a 20 mL screw-top vial. The resulting mixture was placed in a block heater at 120 °C for 5 h. After cooling to room temperature, the resulting purple sample was collected by high-speed centrifugation, then washed three times with fresh dimethylformamide (DMF) and exchanged three times with ethanol, after which the final product was redispersed in ethanol for further use. (X = 80, 130, 180 and 400 μL, relevant sizes = ~80, ~120, ~280 and ~620 nm).

[0197] Different contents of trifluoroacetic acid (TFA) can be utilized to control the particle size of PCN-222. Synthesis of PCN-222(Hf)

[0198] TCPP (10 mg, 12.6 μmol), HfOCl2·8H2O (25 mg, 62.1 μmol), 8 mL of DMF, and 200 μL of TFA were dissolved by ultrasonication in a 20 mL screw-top vial. The resulting mixture was placed in a block heater at 120 °C for 5 h. After cooling to room temperature, the resulting purple sample was collected by high-speed centrifugation, then washed three times with fresh DMF and exchanged three times with ethanol, after which the final product was redispersed in ethanol for further use. Synthesis of UiO-66 (~430 nm)

[0199] 1,4-Benzene carboxylic acid (BDC) (320 mg, 1.93 mmol), ZrCl4 (466 mg, 2.00 mmol), benzoic acid (2.44 g, 20 mmol), and 36 mL of DMF were dissolved by ultrasound in a 100 mL screw-top vial, and then concentrated HCl (0.33 mL) was added. The mixture was heated at 120 °C for 48 h. After cooling to room temperature, the resulting sample was collected by high-speed centrifugation, then washed three times with fresh DMF and exchanged three times with ethanol, and the final product was redispersed in ethanol for further use. Synthesis of MOF-808 (~90 nm)

[0200] 1,3,5-Benzenetricarboxylic acid (70 mg, 0.33 mmol), ZrCl4 (233 mg, 1.00 mmol), formic acid (5.6 mL) and DMF (10 mL) were dissolved by ultrasonication in a 50 mL screw-top vial. The mixture was heated at 120 °C for 48 h. After cooling to room temperature, the resulting sample was collected by high-speed centrifugation, then washed three times with fresh DMF and exchanged three times with ethanol, and the final product was redispersed in ethanol for further use. Synthesis of NU-901 (~240 nm)

[0201] 1,3,6,8-Tetrakis(p-benzoic acid)pyrene (H4TBAPy) (25 mg, 40.4 μmol), ZrOCl2·8H2O (121 mg, 375.5 μmol), 4-aminobenzoic acid (400 mg, 2.92 mmol), TFA (200 μL), and DMF (20 mL) were dissolved by ultrasonication in a 50 mL screw-top vial. The mixture was heated at 140 °C for 50 min, resulting in the formation of a yellow suspension. After cooling to room temperature, the resulting sample was collected by centrifugation, then washed three times with fresh DMF and exchanged three times with ethanol, after which the final product was redispersed in ethanol for further use. Synthesis of PCN-128 (~160 nm)

[0202] (4',4"',4'"",4'"""-(ethene-1,1,2,2-tetrayl)tetrakis([1,10-biphenyl]-4-carboxylate) (ETTC) (10 mg, 12.3 μmol), Zr6 cluster (20 mg, 7.5 μmol), DMF (4 mL), and TFA (100 μL) were dissolved by ultrasonication in a 6 mL screw-top vial. Then, triethylamine (TEA) (20 μL) was added. The mixture was heated at 120 °C for 24 h. After cooling to room temperature, the resulting sample was collected by high-speed centrifugation, then washed three times with fresh DMF and exchanged three times with ethanol, and the final product was redispersed in ethanol for further use. Particle size controlled synthesis and characterization of PCN-222

[0203] PCN-222 is an example of a Zr(IV)-based porphyrin-based MOF. It consists of eight-terminal Zr6 clusters connected to tetrakis(4-carboxyphenyl)porphyrin (TCPP) linkers and features one-dimensional micro- and mesoporous channels with diameters of 1.7 nm and 3.6 nm, respectively.

[0204] First, Zr6 clusters were synthesized as described above. NanoPCN-222 was prepared by the solvothermal reaction of TCPP with Zr6 clusters using trifluoroacetic acid (TFA) as a modifier as previously described (Figure 1). The particle size of PCN-222 can be adjusted by adjusting the amount of TFA used. By increasing the amount of TFA, nanoPCN-222 with larger particle size can be obtained (Figure 26). NanoPCN-222 with a particle size of about 120 nm was selected.

[0205] Powder X-ray diffraction (PXRD) showed the presence of broad peaks consistent with the pattern predicted (simulated) from the single crystal structure, confirming the phase purity of nanoPCN-222 (Figure 2). Figure 13 shows a typical Type IV N2 adsorption isotherm at 77 K for PCN-222.

[0206] Transmission electron microscopy (TEM) imaging confirmed that the PCN-222 nanoparticles had a rod-like morphology and were uniform in size, and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) imaging confirmed the presence of highly oriented mesopores (Figure 27).

[0207] Dynamic light scattering (DLS) of PCN-222 showed a mean hydrodynamic diameter of 118.0 nm ± 0.8 nm and a polydispersity index of 0.104 nm ± 0.009 nm (see Figure 6). The zeta potential (DLS) was 31.7 mV ± 0.4 mV (Figure 7), suggesting that the predominant end groups on the surface are metal (inorganic node) units. Synthesis and characterization of PCN-222@PEG-PO3

[0208] mPEG-PO3 was prepared from a base polymer of poly(ethylene glycol) methyl ether (Mn = 5000 g / mol) in an overall yield of 71%. [ka]

[0209] Nuclear magnetic resonance (NMR) and gel permeation chromatography (GPC) spectra confirmed the formation and purity of mPEG-PO3 (Figures 23, 24, and 25). 31 In the P NMR (Figure 24), only one singlet was observed, indicating one or two PEG chains attached to the phosphate group, while the Mn obtained from GPC (Figure 25) further indicates the presence of one PEG chain. Procedure for PEGylation of PCN-222 (PCN-222@PEG-PO3)

[0210] The mPEG-PO3 solution (10 mL, 25 mg / mL in HO) was added to an aqueous suspension of PCN-222 (5 mL, 10 mg / mL). After stirring for 16 h at room temperature, the reaction mixture was dialyzed (molecular weight cut-off, 12,000 g / mol–14,000 g / mol) against pure deionized water for 12 h to remove unreacted reagents. The deionized water was decanted and replenished with fresh one (20 mL, 80 mM) every 4 h. The resulting PCN-222@PEG-PO3 suspension was either lyophilized using a Telstar LyoQuest benchtop freeze dryer (0.008 mBar, -70 °C) to yield a relatively low-density brown product or recovered by centrifugation (18000 rpm, 35 min), washed with ethanol, and air-dried to yield a relatively high-density, dark-colored product.

[0211] The final amount of PEG loaded in the PCN-222@PEG-PO3 nanoparticles was determined by the ratio of phosphate (mPEG-PO3) to zirconium (PCN-222), as shown in Table 1 below.

[0212] The PEGylation methods of UiO-66@PEG-PO3, MOF-808@PEG-PO3, NU-901@PEG-PO3 and PCN-128@PEG-PO3 were essentially the same as that of PCN-222@PEG-PO3. Dry PCN-222@PEG-PO3

[0213] It was shown that the method of drying PCN-222@PEG-PO3 influenced the morphology of the resulting dry powder.

[0214] The final product aqueous suspension was spun down, exchanged with ethanol, and then dried under ambient conditions (room temperature and pressure), resulting in a relatively dense, dark-colored sample (Figure 30a).

[0215] On the other hand, freeze-drying the suspension yielded a brown, relatively low density material (Figure 10 inset and Figure 30b).

[0216] The results showed that the air-dried samples were largely aggregated, whereas the freeze-dried samples were easily redispersed by ultrasonic treatment to form a pink suspension (Figure 10, inset). The characteristic Tyndall effect was observed when passing a red laser beam through the redispersed suspension, revealing its colloidal nature.

[0217] To visualize the presence of mPEG-PO3 in PCN-222@PEG-PO3, scanning electron microscopy (SEM) of the dried samples was performed (Figures 31 and 32). The SEM images revealed that PCN-222@PEG-PO3 was densely packed, uniformly dispersed, and had a rod-like morphology.

[0218] For freeze-dried PCN-222@PEG-PO3, nano-MOFs were clearly observed to be tightly embedded within the matrix. Without being bound by theory, it is believed that the surface-bound mPEG-PO3 molecules (Figure 7, Figure 32) could act as particle partitions, leading to the formation of independent PCN-222@PEG-PO3 particles, which in turn formed the matrix.

[0219] On the other hand, SEM of air-dried PCN-222@PEG-PO3 showed that monodisperse particles were randomly packed into centimeter-sized three-dimensional superstructures, with the absence of the matrix observed in the freeze-dried sample. This indicates that the mPEG-PO3 molecules are tightly packed around the particles in the air-dried sample. Also, the surface of the air-dried PCN-222@PEG-PO3 nano-MOF is rougher compared to the parent PCN-222, which is because the surface features of the air-dried PCN-222@PEG-PO3 are dominated by the bulk of the capping polymer, which forms nanopapillae on the surface, making the surface relatively rough. Incorporation of mPEG-PO3 into PCN-222@PEG-PO3

[0220] According to Table 1, the incorporation amount of mPEG-PO3 in PCN-222@PEG-PO3 is found to be 32.9% based on the weight of the coated particles by measuring the ratio of P to Zr using inductively coupled plasma-optical emission spectroscopy (ICP-OES). [Table 1]

[0221] The material was characterized to demonstrate the PEGylation of PCN-222. The PXRD of PCN-222@PEG-PO3 correlated well with the parent and simulated patterns, thereby confirming the crystallinity of PCN-222 after PEGylation. The presence of two new peaks centered at 2θ = 19.0° and 23.2° originates from the high molecular weight and semi-crystalline PEG in PCN-222@PEG-PO3 (Figure 12).

[0222] The Fourier transform infrared (FT-IR) spectrum further confirmed the presence of mPEG-PO3. -1 and 1088cm -1 The appearance of two new bands at 1095 cm can be attributed to the CH and PO stretching vibrations of the mPEG-PO3 molecule, respectively (Figure 33a). In particular, the FT-IR absorption of the PO bond in PCN-222@PEG-PO3 is significantly higher at 1095 cm than that in mPEG-PO3. -1 From 1088cm -1 A shift to 0.01 was observed (Figure 33b), indicating the presence of interactions between the Zr6 clusters and the phosphate groups and the fact that all the phosphate groups of the incorporated mPEG-PO3 participate in the coordination and are not simply adsorbed on the outer surface.

[0223] TEM images of the drop-cast PCN-222@PEG-PO3 clearly show the well-preserved morphology of the parent MOF and the overall monodisperse particles (Figures 8 and 9 for PCN-222 and PCN-222@PEG-PO3, respectively). Furthermore, HAADF-STEM imaging shows that the highly ordered mesopores are maintained after PEGylation (Figure 28).

[0224] DLS was further employed to investigate the effect of PEGylation on the dispersibility of PCN-222. PEGylation of PCN-222 resulted in particles with a diameter of 129.7 nm ± 0.9 nm, slightly larger than that of the parent PCN-222 (Figure 6). At the same time, the polydispersity index also decreased to 0.076 nm ± 0.004 nm. Without being bound by theory, this can be explained by the dispersion of small aggregates of the parent PCN-222 during the PEGylation process.

[0225] From Fig. 7, it can be seen that the attachment of terminal phosphate groups to the outer surface of the PCN-222 sample caused the zeta potential to become more negative, from 31.7 mV ± 0.4 mV for parent PCN-222 to − 43.9 mV ± 1.2 mV for PCN-222@PEG-PO3.

[0226] 31 The interaction of mPEG-PO3 with the framework was investigated using P solid-state nuclear magnetic resonance (SSNMR) and X-ray photoelectron (XPS) spectra. Figure 3 shows the chemical shift of phosphorus resonance in free mPEG-PO3 and PCN-222@PEG-PO3 in the solid state. Free mPEG-PO3 exhibits a sharp peak around -0.30 ppm, and after PEGylation of PCN-222, the peak becomes broad and upshifts to -8.39 ppm. The shift of phosphorus resonance indicates the interaction between the phosphate group of mPEG-PO3 and MOF. XPS investigation and high resolution P 2p spectrum confirmed the presence of phosphorus in PCN-222@PEG-PO3 (Figures 4 and 35), which belongs to the phosphorus of incorporated mPEG-PO3.

[0227] Furthermore, the high-resolution Zr 3d spectrum shows that the 3d Zr(IV) of the parent PCN-222 3 / 2 and 3D 5 / 2 The two main peaks at around 184.4 eV and 182.0 eV, which are attributed to , are downshifted to 183.5 eV and 181.1 eV, respectively (see Figure 5).

[0228] Without being bound by theory, we suspect that the shift in binding energy to the lower energy side is due to the replacement of TFA coordinated to the Zr-O cluster of PCN-222 with mPEG-PO3 in PCN-222@PEG-PO3. Compared with the trifluoroacetate group of TFA, the phosphate group of mPEG-PO3 has a lower electronegativity. This binding reduces the loss of electron density of Zr, which reduces the binding energy of the 3d electrons. From Figure 4, we can see that the F 1s peak at 688.2 eV of the parent PCN-222 is significantly weaker after PEGylation, which indicates a decrease in the amount of TFA binding.

[0229] Taken together, the chemical resonance and binding energy shifts after PEGylation indicate the formation of Zr-OP coordinate bonds. Effect of mPEG-PO3 on the internal void

[0230] Next, to investigate the effect of incorporating mPEG-PO3 into the internal voids of PCN-222, N2 uptake experiments were carried out at 77 K. As shown in Fig. 13, PCN-222 and PCN-222@PEG-PO3 had N2 uptake rates of 526 cm3 at P / P0 = 0.8, respectively. 3 g -1 and 129cm 3 g -1 It adsorbs N2.

[0231] Assuming that the contained mPEG-PO3 is on the outer surface of nanoPCN-222, the ideal N2 uptake amount at P / P0 = 0.8 is 353 cm3g-1, which is the amount of contained mPEG-PO3 (Table 2), and the actual value obtained this time (129 cm3g-1) is 1. 3 g -1N2) is 36.5% of the ideal N2 uptake.

[0232] Without being bound by theory, the discrepancy between the ideal and experimental values ​​may be due to the penetration of mPEG-PO3 molecules into the internal voids of nanoPCN-222 after 16 h of PEGylation. Furthermore, the pore size distribution (PSD) obtained using the nonlocal density functional theory (NLDFT) method also reveals a decrease in porosity (Figure 14), further demonstrating that the present invention modifies the MOF nanoparticle surface at the partial expense of porosity. Time-dependent considerations

[0233] The PEGylation of PCN-222 was studied in terms of time dependence by quenching the reaction for different reaction times, and the intermediates were analyzed by several ex situ spectroscopic and microscopic characterizations. These resulting PEGylated PCN-222 were named PEGylated xh, where x is the reaction time (x = 2, 4, 12, 16). Synthesis for time-dependent studies

[0234] To four identical vials containing 5 mL of water suspension of 120 nm size PCN-222 (10 mg / mL), 10 mL of mPEG-PO3 solution (25 mg / mL in H2O) was added respectively. The mixtures were stirred (800 rpm) at room temperature for 2, 4, 12 and 16 h.

[0235] At each time point, one sample was centrifuged to remove unreacted mPEG-PO3, and subsequently it was placed in a dialysis tube (molecular weight cut-off, 12,000 g / mol–14,000 g / mol) and dialyzed against pure deionized water for 12 h. The deionized water was decanted and replenished with new one (20 mL, 80 mM) every 4 h.

[0236] The resulting suspension was lyophilized using a Telstar LyoQuest benchtop freeze dryer (0.008 mBar, -70 °C) to give the desired product, named PEGylated xh (x is the reaction time), which was used for further characterization. Results of time-dependent study

[0237] Figure 12 and Figure 33a show that their PXRD patterns and FT-IR spectra do not change significantly throughout the PEGylation process. ICP-OES quantifies the amount of mPEG-PO3 incorporated at different PEGylation times by measuring the ratio of Zr to P (Table 1). The results show that the loading of mPEG-PO3 after 2 hours is 27.8 wt%, and plateaus around 33 wt% with increasing reaction time.

[0238] Moreover, the thermogravimetric analysis (TGA) profiles also show a similar trend (Figure 34). The amount of encapsulated mPEG-PO3 was calculated based on the difference from the first plateau (376°C to 452°C) in the TGA curve.

[0239] To investigate the position of mPEG-PO3 when the reaction time was changed, the N2 adsorption characteristics were examined. After 2 hours, the N2 uptake was 348 cm3 at P / P0 = 0.8. 3 g -1 (Figure 13), which accounted for 91.6% of the ideal N2 uptake (Table 2). Without being bound by theory, this is believed to be because PEGylation occurs mainly on the surface, with a small amount of mPEG-PO3 molecules or PEG chains of surface-bound mPEG-PO3 penetrating into the voids. [Table 2]

[0240] The effect of mPEG-PO3 on porosity after 2 h can be more easily observed if the amount of bound mPEG-PO3 is subtracted. As shown in Figure 37, the N2 isotherm and PSD results indicate that the decrease in the N2 isotherm and PSD is small. Again, without being bound by theory, this result also suggests that PEGylation occurs mainly on the surface in the initial stage. After that, with 4 h of continuous PEGylation, the amount of mPEG-PO3 increased to 33.3 wt% (Table 1), and the corresponding N2 uptake at P / P0 = 0.8 was 124 cm. 3 g -1The N2 uptake was reduced to 0.01 mg / kg / day, which is 35.3% of the ideal N2 uptake (Table 2). These values ​​remained constant for longer reactions at 12 and 16 hours (Figure 13), indicating that the PEGylation reached equilibrium and the mPEG-PO3 molecules entered the pores of the particles. Without being bound by theory, it is believed that the excess mPEG-PO3 molecules began to permeate into the channels after essentially completely occupying all available binding sites on the exterior surface.

[0241] These results indicate that a two-step PEGylation process of PCN-222 with mPEG-PO3 is proposed. Without being bound by theory, the electrostatic interaction between the positively charged PCN-222 and the negatively charged mPEG-PO3 first leads to PEGylation on the outer surface. After occupying the available binding sites on the surface, the unreacted mPEG-PO3 molecules start to enter the inner channels of PCN-222, decreasing the porosity (Figure 11). Elemental Mapping

[0242] Elemental mapping was performed using energy dispersive X-ray spectroscopy (EDX) in a STEM. However, since the La line of Zr is 2.042 keV and the Ka line of P is 2.012 keV, the energy window of P overlaps with that of Zr, leading to misidentification of the element.

[0243] We solved this problem by replacing Zr-based PCN-222 with Hf-based PCN-222 (denoted as PCN-222(Hf)) to form an alternative polymer-coated nanoparticle MOF. PXRD and N2 isotherms confirmed the crystallinity and porosity of PCN-222(Hf) (Figures 15, 38, 40), and STEM imaging and XPS spectra clearly showed the rod morphology of PCN-222(Hf) and the presence of Hf (Figures 16, 36).

[0244] Under the same PEGylation conditions as for Zr-based PCN-222, ex situ STEM-EDX was obtained for PCN-222(Hf) after 2, 4, 12, and 16 h to map the distribution of P and Hf. After 2 h, the Hf signal was found to be uniformly distributed throughout the particle, whereas the P signal mainly originated from the edge, providing further evidence that the mPEG-PO3 molecules are primarily grafted to the surface at the initial stage. As the reaction time progresses from 4 to 16 h, the P signal is uniformly distributed throughout the particle.

[0245] Additionally, EDX line scans of PCN-222(Hf) after 16 h of PEGylation were also performed, which demonstrated homogeneous distribution of Hf and P along single particles. The results observed here are in excellent agreement with the previously described TGA, N2 uptake, and ICP-OES, confirming that PEGylation of PCN-222 and PCN-222(Hf) nanoparticles with mPEG-PO3 proceeds in two steps (Figure 11). Versatility of the Phosphate-Coordinated PEGylation Method

[0246] The above PEGylation method was extended to four additional Zr-based MOFs, UiO-66, MOF-808, NU-901, and PCN-128 (Figure 29). The related lyophilized PEGylated MOFs were successfully obtained and designated MOF@PEG-PO3, using the same nomenclature as for PCN-222.

[0247] When the MOF@PEG-PO3 was illuminated with a red laser, a pronounced Tyndall effect was recorded. Figure 17 shows the retention of crystallinity after PEGylation and the presence of semi-crystalline PEG, which was evidenced by PXRD studies. The N2 isotherms and PSDs show that all voids are partially filled by the infiltrated mPEG-PO3, similar to PCN-222@PEG-PO3 (Figures 39 and 41).

[0248] The loadings of incorporated mPEG-PO3 molecules evaluated by ICP-OES are 37.7 wt%, 38.5 wt%, 30.6 wt%, and 34.1 wt% for UiO-66@PEG-PO3, MOF-808@PEG-PO3, NU-901@PEG-PO3, and PCN-128@PEG-PO3, respectively (Table 1).

[0249] All the freeze-dried MOF@PEG-PO3 have a relatively low density, and the SEM images of the freeze-dried MOF@PEG-PO3 show that the particles are uniformly distributed within the matrix formed by the incorporated mPEG-PO3 molecules (Figures 18, 19, 20, and 21).

[0250] Importantly, all of the MOF@PEG-PO3 nanoparticles could be easily redispersed in water after mild sonication, and their hydrodynamic diameters were not significantly different compared to the suspensions before lyophilization (Figure 22).

[0251] The colloidal stability of these MOF@PEG-PO3 in water and phosphate buffered saline (PBS; pH=7.4) was evaluated. Figures 41 and 42 show that the suspension of PEGylated MOF in water is stable for up to 7 days without significant change in its hydrodynamic particle size, which is superior to bare MOF, which aggregates significantly over time. In PBS (pH=7.4), MOF@PEG-PO3 can maintain its hydrodynamic particle size for 36 hours.

[0252] On the other hand, the pristine MOF nanoparticles precipitated in a very short time, for example within one day.

[0253] These results confirm that the polymer coating method disclosed herein not only retards aggregation in aqueous and biological media but also serves as a versatile strategy as an alternative for the long-term storage of MOF-based drug carriers. Controlled release study - DOX@PCN-222@PEG-PO3

[0254] The polymer-coated MOF nanoparticles of the present invention can be used to encapsulate active ingredients, as described herein above. The release profile of the encapsulated active ingredient from the polymer-coated MOF nanoparticles is particularly advantageous compared to the active ingredient release profile of uncoated MOF nanoparticles.

[0255] For MOF nanoparticles encapsulating an active ingredient, we refer to them as active ingredient@MOF for uncoated MOF nanoparticles and active ingredient@MOF@polymer for polymer-coated MOF nanoparticles. For example, doxorubicin (DOX) encapsulated in PCN-222 and PCN-222@PEG-PO3 is represented as DOX@PCN-222 and DOX@PCN-222@PEG-PO3, respectively. Preparation of DOX@PCN-222

[0256] 20 mg of PCN-222 was immersed in a 15 mg / mL solution of doxorubicin (DOX) in deionized H2O for 24 h at room temperature. The resulting DOX-loaded PCN-222 (DOX@PCN-222) was then collected by centrifugation at 14000 rpm for 20 min and washed with deionized water to remove the bioadsorbed DOX molecules on the surface. The resulting DOX@PCN-222 was then dried in a vacuum oven at room temperature for 24 h. Preparation of DOX@PCN-222@PEG-PO3

[0257] 20 mg of PCN-222 was immersed in a 15 mg / mL solution of DOX in deionized H2O for 24 h at room temperature. The resulting DOX-loaded PCN-222 (DOX@PCN-222) was then collected by centrifugation at 14000 rpm for 20 min, and 5 equivalents (mass ratio) of mPEG-PO3 were added and stirred for another 16 h. The final sample was collected by centrifugation at 14000 rpm for 20 min and washed with deionized water to remove the physisorbed DOX molecules on the surface. The resulting DOX@PCN-222@PEG-PO3 was then dried in a Telstar LyoQuest benchtop freeze dryer (0.008 mBar, -70 °C).

[0258] To examine the degree of drug (DOX) loading, the supernatant of the centrifuged solution was collected and subjected to UV-visible spectroscopy at 482 nm. The recorded absorption intensity was compared with a calibration curve plotted for free DOX to identify the drug concentration. Controlled Release Testing

[0259] Samples loaded with 8 mg of DOX were kept in a dialysis bag (molecular cutoff: 12,000–14,000 Da). The dialysis bag was immersed in 30 mL of deionized water and stirred at room temperature. The released DOX concentration was measured every 2 h by removing 3 mL of the supernatant and analyzing it at 482 nm with a UV-Visible spectrometer. After the end of each measurement, the volume was kept constant by adding the removed solvent.

[0260] As shown in Figure 43, the release of DOX from uncoated MOF nanoparticles (PCN-222) is significantly faster than that from polymer-coated MOF nanoparticles (PCN-222@PEG-PO3). Approximately 40% of the DOX release was recorded after 6 h from DOX@PCN-222, whereas approximately 40% of the DOX release was recorded after 40 h from DOX@PCN-222@PEG-PO3. Controlled release studies - further exemplary DOX@MOF@PEG-PO3

[0261] Further studies were conducted to demonstrate the advantageous, controlled, sustained release of active ingredients, particularly active pharmaceutical ingredients, from the polymer coated metal-organic framework nanoparticles of the present invention. DOX-loaded MOF

[0262] DOX@MOF: An aqueous suspension of as-synthesized nanoMOFs (5 mg / mL, 6 mL) was added to an aqueous DOX solution (15 mg / mL, 4 mL) and then stirred at room temperature for 48 h. The DOX-loaded nanoMOFs were then collected by centrifugation (15,000 rpm, 35 min) and washed three times with water. The resulting DOX@MOFs were either dried under vacuum or redispersed in water for further use. The unloaded DOX was combined and diluted to a final volume of 500 mL to determine the DOX loading.

[0263] DOX@MOF@PEG-PO3: To an aqueous DOX solution (15 mg / mL, 4 mL), an aqueous suspension of as-synthesized nanoMOFs (5 mg / mL, 6 mL) was added, and the mixture was then stirred at room temperature for 48 h. Then, an aqueous mPEG-PO3 solution (6 mL, 25 mg / mL) was directly added, and the resulting mixture was stirred for another 16 h. The reaction mixture was then centrifuged (15,000 rpm, 35 min) to remove unreacted mPEG-PO3 and unloaded DOX, redispersed in water, and then dialyzed (MWCO, 12,000–14,000) against water for 12 h. The water was decanted and replenished with fresh water every 4 h. The final suspension was lyophilized (0.008 mBar, −70 °C) or vacuum dried. The unloaded DOX was combined and diluted to a final volume of 500 mL to determine the DOX loading.

[0264] The absorbance was measured by UV-Vis spectroscopy (maximum absorbance at 486 nm). Concentrations were calculated by comparing the UV-Vis absorbance with a standard curve.

[0265] Drug loading (wt%) = (mass of drug used - mass of unloaded drug) / mass of MOF × 100 Drug release

[0266] 10 mg of DOX@MOF and DOX@MOF@PEG-PO3 were suspended in 2 mL of PBS (pH = 7.4) and placed in a dialysis bag (MWCO; 1,2000-1,4000) dispersed with 2 mL of PBS (pH = 7.4) and dialyzed against PBS (pH = 7.4) (28 mL) under magnetic stirring at room temperature. At regular intervals, 1 mL of PBS (pH = 7.4) was taken out and replaced with a new one. The released drugs were analyzed by fluorescence spectroscopy by comparing with a calibration curve with a mission maximum at 595 nm when excited at 486 nm. Drug loading results

[0267] UV-visible spectroscopy confirmed DOX loading of 21.3 wt%, 16.8 wt%, 28.5 wt%, 22.1 wt%, and 30.2 wt% for pristine UiO-66, MOF-808, NU-901, PCN-128, and PCN-222. PEGylation showed only a slight decrease of 17.8 wt%, 15.5 wt%, 25.3 wt%, 15.8 wt%, and 18.4 wt%, respectively (see FIG. 44). Without being bound by theory, this is believed to be due to the replacement of a small amount of loaded DOX by infiltration of mPEG-PO3. Drug release results

[0268] The cumulative release of both DOX@MOF and DOX@MOF@PEG-PO3 was monitored in PBS (pH = 7.4) for up to 200 h. Figure 45 shows the release kinetics of NU-901, PCN-128, and PCN-222, respectively.

[0269] For NU-901, PCN-128, and PCN-222, the release profiles of DOX@MOF@PEG-PO3 were dramatically decreased in the PEGylated samples compared to those of bare (uncoated) nanoMOFs, with less than 20 wt% of the encapsulated DOX released in the first 6 h. In contrast, bare nanoMOFs released 38.4 wt%, 40.1 wt%, and 52.5 wt% of DOX, respectively.

[0270] These results demonstrate that polymer-coated MOF nanoparticles are capable of a slower, more sustained release, which may be particularly advantageous for sustained delivery of active ingredients, particularly drugs, which may facilitate less frequent drug administration, especially compared to direct drug delivery or delivery from uncoated MOF nanoparticles.

[0271] Without being bound by theory, it is believed that the polymer-coated nanoparticles of the present invention may be particularly effective as a result of the relatively strong bonds (e.g., phosphate-metal coordination) between the polymer and the MOF nanoparticles, avoiding release of the polymer in solution (dumping) and the subsequent rapid dispersion of the drug. By varying the amount and type of polymer used, the drug release profile can be tuned.

[0272] In particular, the use of linear polymers, especially linear polyethylene glycols and their derivatives, has been found to be effective, and without being bound by theory, it is believed that this is because the linear nature of the polymers helps to separate and redisperse the nanoparticles well.

[0273] Thus, advantageously, lyophilized, polymer-coated, drug-containing MOF nanoparticles may have improved shelf life, reduced aggregation for easier redispersion, and provide tunable, sustained release.

[0274] All documents cited herein (including any cross-referenced or related patents or applications) are hereby incorporated by reference in their entirety unless expressly excluded or otherwise limited.

[0275] It will be understood that various modifications can be made to the illustrated embodiments without departing from the spirit and scope of the present invention as defined by the appended claims.

[0276] Aspects of the invention are further described with reference to the following numbered paragraphs. 1. 1. A dry powder pharmaceutical composition comprising one or more lyophilized, polymer-coated metal-organic framework (MOF) nanoparticles, Each nanoparticle contains a MOF that includes a plurality of metal ions and a plurality of organic ligands, and has a particle size of about 25 nm to about 450 nm; The polymer binds to one or more metal ions, A composition, wherein at least one active pharmaceutical ingredient is present on and / or in one or more of the lyophilized, polymer-coated MOF nanoparticles, and preferably the polymer is bound to one or more metal ions of each nanoparticle by phosphate-metal coordination. 2. A pharmaceutical composition comprising the dry powder pharmaceutical composition of item 1 in a state of being mixed in a liquid, preferably the liquid is aqueous, preferably the composition further comprises a pharma- ceutically acceptable excipient, preferably the excipient is selected from the group consisting of solvents, cosolvents, buffers, stabilizers, antioxidants, preservatives, chelating agents, emulsifiers, flavorings, lubricants, suspending agents, isotonicity agents, surfactants, solubilizers, suspension aids, dispersing agents, moisturizers, thickeners, colorants, wetting agents, antifoaming agents, viscosity adjusters, sweeteners, and combinations thereof. 3. 1. A composition comprising one or more polymer-coated metal-organic framework (MOF) nanoparticles, each nanoparticle comprising a MOF comprising a plurality of metal ions and a plurality of organic ligands, the polymer being bound to the one or more metal ions of each nanoparticle by phosphate-metal coordination, and the one or more polymer-coated MOF nanoparticles having a particle size of about 25 nm to about 450 nm. 4. The composition according to item 3, wherein an active ingredient is encapsulated in and / or present on one or more MOF nanoparticles coated with said polymer, preferably said active ingredient is an active pharmaceutical ingredient. 5. 1. A method for producing a dry powder composition containing one or more polymer-coated metal-organic framework (MOF) nanoparticles, each nanoparticle containing a MOF comprising a plurality of metal ions and a plurality of organic ligands, the polymer being bound to the one or more metal ions, the polymer-coated one or more MOF nanoparticles having a particle size of about 25 nm to about 450 nm, the method comprising: a) mixing a plurality of metal ions and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; b) mixing the suspension of the one or more uncoated MOF nanoparticles with the polymer, wherein the polymer binds to one or more metal ions of the one or more uncoated MOF nanoparticles to provide a suspension of one or more MOF nanoparticles coated with the polymer; c) Optionally, concentrating the polymer-coated MOF nanoparticle suspension by removing the solvent; d) drying the polymer-coated one or more MOF nanoparticles by lyophilization; Including, Preferably prior to step b), the active ingredient is encapsulated within and / or present on the polymer-coated one or more MOF nanoparticles, preferably by mixing the active ingredient with a suspension of the uncoated one or more MOF nanoparticles. 6. 13. A method for producing a suspension of polymer-coated MOF nanoparticles, the method comprising the steps of taking a dry powder composition produced according to paragraph 5 and resuspending the composition in a liquid, preferably wherein the liquid is aqueous. 7. 1. A method for producing a composition containing one or more polymer-coated metal-organic framework (MOF) nanoparticles containing an active ingredient, each nanoparticle containing a MOF that includes a plurality of metal ions and a plurality of organic ligands and has a particle size of about 25 nm to about 450 nm, the polymer being bound to the one or more metal ions by phosphate-metal coordination, the method comprising: a) mixing a plurality of metal ions and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; b) providing a suspension of one or more uncoated MOF nanoparticles containing an active ingredient by encapsulating said active ingredient in and / or presenting said active ingredient on said one or more uncoated MOF nanoparticles; c) mixing a suspension of the one or more uncoated MOF nanoparticles containing the active ingredient with a polymer functionalized with phosphate groups, and allowing the polymer functionalized with phosphate groups to coordinate to one or more metal ions of the one or more uncoated MOF nanoparticles containing the active ingredient, thereby providing a suspension of one or more polymer-coated MOF nanoparticles containing the active ingredient; d) Optionally, concentrating the suspension of one or more polymer-coated MOF nanoparticles containing the active ingredient by removing the solvent; e) Optionally, drying the polymer-coated one or more MOF nanoparticles containing the active ingredient by lyophilization; f) Optionally, thereafter, redispersing the freeze-dried polymer-coated MOF nanoparticles containing the active ingredient in an aqueous medium; The method includes: 8. 1. A method for producing a composition containing one or more metal-organic framework (MOF) nanoparticles coated with methoxypolyethylene glycol (mPEG), each nanoparticle comprising a MOF comprising a plurality of metal ions and a plurality of organic ligands and having a particle size of about 25 nm to about 450 nm, wherein the mPEG is bound to the one or more metal ions by phosphate-metal coordination, the method comprising: a) mixing a plurality of metal ions and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; b) mixing the suspension of the one or more uncoated MOF nanoparticles with a solution of mPEG-PO3, and coordinating mPEG-PO3 to one or more metal ions of the one or more uncoated MOF nanoparticles, thereby providing a suspension of one or more MOF nanoparticles coated with mPEG-PO3; c) Optionally, concentrating the mPEG-coated MOF nanoparticle suspension by removing the solvent; d) Optionally, drying the mPEG-coated one or more MOF nanoparticles by lyophilization; e) Optionally, redispersing the lyophilized mPEG-coated MOF nanoparticles, preferably by sonication; Preferably prior to step b), an active ingredient is made present on and / or encapsulated in said m-PEG-coated one or more MOF nanoparticles, preferably by a step of mixing an active ingredient with a suspension of said uncoated one or more MOF nanoparticles. 9. 9. The composition or method according to any one of items 1 to 8, wherein the plurality of metal ions consists essentially of metal ions selected from the group consisting of zirconium, iron, zinc, and hafnium. 10. The composition or method according to any one of items 1 to 7 and item 9 when dependent on items 1 to 7, wherein the polymer comprises a phosphate group, preferably a terminal phosphate group, preferably the polymer is selected from the group consisting of polyethylene glycol, hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof, preferably the polymer comprises polyethylene glycol or a derivative thereof, preferably a phosphate-terminated mPEG, preferably the polymer and / or mPEG-PO3 is a phosphate-terminated mPEG according to Structure A. [ka] In the formula, n is about 40 to about 250. 11. 11. The composition or method according to any one of items 1 to 10, wherein the particle size of the one or more MOF nanoparticles coated with the polymer is about 100 nm to about 250 nm, preferably about 100 nm to about 200 nm. 12. A composition produced according to any of the above methods of items 5 to 8 and / or a composition according to any one of items 1 to 4 or 9 to 11, wherein the one or more MOF nanoparticles are at least partially amorphous. 13. 1. Use of a polymer functionalized with phosphate groups for coating one or more MOF nanoparticles, wherein an active ingredient is present in and / or on one or more MOF nanoparticles coated with said polymer. 14. 13. The use of a polymer to improve redispersion of freeze-dried MOF nanoparticles, wherein the polymer is coated onto the MOF nanoparticles prior to freeze-drying. 15. A method for treating a disease or condition by administering the composition according to any one of items 1 to 4 or 9 to 12 to a patient.

Claims

1. A composition comprising one or more metal-organic framework (MOF) nanoparticles coated with a polymer, comprising: Each nanoparticle contains a MOF that includes a plurality of metal ions and a plurality of organic ligands; The polymer binds to one or more of the metal ions of each MOF nanoparticle by phosphate-metal coordination; The particle size of the MOF nanoparticles coated with one or more polymers is between 25 nm and 450 nm as measured by dynamic light scattering; The polymer comprises one terminal phosphate group. composition.

2. The composition of claim 1, wherein an active ingredient is encapsulated in and / or present in one or more MOF nanoparticles coated with the polymer, and the active ingredient is an active pharmaceutical ingredient.

3. A method for producing a composition containing one or more metal-organic framework (MOF) nanoparticles containing an active ingredient coated with a polymer, each nanoparticle containing a MOF comprising a plurality of metal ions and a plurality of organic ligands and having a particle size between 25 nm and 450 nm; the polymer is bound to the one or more metal ions by phosphate-metal coordination, each polymer comprising one terminal phosphate group; The method comprises: a) mixing a plurality of metal ions and a plurality of organic ligands to form a suspension of one or more uncoated MOF nanoparticles; b) encapsulating an active ingredient in and / or in the presence of an active ingredient in said uncoated one or more MOF nanoparticles to provide a suspension of uncoated one or more MOF nanoparticles containing the active ingredient; c) subsequently, mixing the suspension of the one or more uncoated MOF nanoparticles containing the active ingredient with a phosphate-functionalized polymer, and allowing the phosphate-functionalized polymer to coordinate to the one or more metal ions of the one or more uncoated MOF nanoparticles containing the active ingredient, to provide a suspension of one or more MOF nanoparticles containing the active ingredient and coated with the polymer; A method comprising:

4. The method further comprising: d) - concentrating the suspension of one or more MOF nanoparticles containing the active ingredient and coated with a polymer by removing the solvent; The method of claim 3 , comprising:

5. The method further comprising: e) drying the one or more MOF nanoparticles containing the active ingredient and coated with polymer by freeze-drying; The method of claim 3 or claim 4, comprising:

6. The method according to claim 1, further comprising: f) subsequently redispersing the freeze-dried active ingredient-containing polymer-coated MOF nanoparticles in an aqueous medium; The method according to any one of claims 3 to 5, comprising:

7. 3. The composition of claim 1 or claim 2, wherein the plurality of metal ions consists essentially of metal ions selected from the group consisting of zirconium, iron, zinc, and hafnium.

8. 8. The composition of claim 1, claim 2 or claim 7, wherein the polymer is substantially linear.

9. The composition according to any one of claims 1, 2 and 7 to 8, wherein the polymer is selected from the group consisting of polyethylene glycol (PEG), hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof.

10. The composition of any one of claims 1, 2 and 7 to 9, wherein the polymer is a phosphate-terminated mPEG according to structure A. 【Chemistry 1】 In the formula, n is 40 to 250.

11. The composition according to any one of claims 1, 2 and 7 to 10, wherein the particle size of each of the polymer-coated MOF nanoparticles is between 100 nm and 250 nm as measured according to the dynamic light scattering method.

12. A composition produced according to any of the methods of claims 3 to 5, and / or a composition according to any one of claims 1, 2 or 7 to 11, wherein the one or more nanoparticles are at least partially amorphous.

13. 1. Use of a polymer to improve redispersion of freeze-dried MOF nanoparticles, said polymer being coated onto said MOF nanoparticles prior to freeze-drying.

14. A composition according to any one of claims 1, 2 or 7 to 12 for use in therapy.

15. The method of any one of claims 3 to 6, wherein the plurality of metal ions essentially consist of metal ions selected from the group consisting of zirconium, iron, zinc, and hafnium.

16. The method of claim 3, wherein the polymer is substantially linear.

17. The method of any one of claims 3 to 6 and claims 15 to 16, wherein the polymer is selected from the group consisting of polyethylene glycol (PEG), hyaluronic acid, heparin, chitosan, polyvinyl alcohol, polyglutamic acid, and derivatives and copolymers thereof.

18. The method of any one of claims 3 to 6 and claims 15 to 17, wherein the polymer is a phosphate-terminated mPEG having structure A. 【Chemistry 2】 In the formula, n is 40 to 250.

19. The method of any one of claims 3 to 6 and claims 15 to 18, wherein the particle size of each of the polymer-coated MOF nanoparticles is between 100 nm and 250 nm as measured according to the dynamic light scattering method.